Ceria-based composite microparticle dispersion, its manufacturing method and polishing abrasive dispersion containing the ceria-based composite microparticle dispersion
The ceria-based composite fine particle dispersion, featuring amorphous silica base particles with crystalline ceria child particles, addresses low polishing rates and impurity issues, providing high-speed, precise, and stable polishing for semiconductor substrates.
Patent Information
- Application Number
- JP2021099386
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-06-15
- Publication Date
- 2025-01-23
- Estimated Expiration
- 2041-06-15
AI Technical Summary
Existing ceria-based abrasive particles for semiconductor polishing exhibit low polishing rates, surface defects, and impurity issues, leading to reduced precision and stability, particularly in the polishing of silicon oxide and silicon nitride films.
A ceria-based composite fine particle dispersion is developed, comprising amorphous silica base particles with crystalline ceria child particles dispersed within a cerium-containing silica layer, characterized by specific geometric relationships and particle size distributions, produced through a method involving controlled pH, redox potential, and calcination steps.
The dispersion achieves high-speed polishing with reduced impurities, improved surface precision, and enhanced stability, suitable for polishing silica films and semiconductor substrates with minimal scratches and residue.
Smart Images

Figure 0007620504000002 
Figure 0007620504000003 
Figure 0007620504000004
Abstract
Description
[Technical Field]
[0001] The present invention relates to a ceria-based composite microparticle dispersion suitable as an abrasive used in the manufacture of semiconductor devices and the like, and in particular to a ceria-based composite microparticle dispersion for planarizing a film to be polished formed on a substrate by chemical mechanical polishing (CMP), a method for producing the same, and a polishing abrasive dispersion containing the ceria-based composite microparticle dispersion. [Background technology]
[0002] Higher performance is being achieved through increased density and miniaturization of semiconductor devices such as semiconductor substrates and wiring boards. Chemical mechanical polishing (CMP) is used in the semiconductor manufacturing process, and is an essential technology for shallow trench isolation, planarization of interlayer insulating films, and formation of contact plugs and Cu damascene wiring.
[0003] Generally, CMP abrasives consist of abrasive grains and chemical components, with the chemical components accelerating polishing by oxidizing or corroding the target film. Meanwhile, the abrasive grains polish through mechanical action, and colloidal silica, fumed silica, and ceria particles are used as abrasive grains. Ceria particles in particular exhibit a particularly high polishing rate for silicon oxide films, and are therefore used in polishing shallow trench isolation processes. In the shallow trench isolation process, not only the silicon oxide film but also the silicon nitride film is polished. To facilitate isolation, it is desirable that the polishing rate of the silicon oxide film is high and the polishing rate of the silicon nitride film is low, and this polishing rate ratio (selectivity) is also important.
[0004] Conventionally, the polishing method for such components involves a relatively rough primary polishing process followed by a precise secondary polishing process to obtain a smooth surface or an extremely high-precision surface with few scratches or other imperfections. Regarding the abrasive used in the secondary polishing as the finish polishing, the following methods have been proposed.
[0005] For example, Patent Document 1 describes a method for producing cerium oxide ultrafine particles (average particle diameter 10 to 80 nm) made of cerium oxide single crystals, which comprises mixing and stirring an aqueous solution of cerous nitrate and a base in a ratio such that the pH is 5 to 10, followed by rapidly heating to 70 to 100°C and aging at that temperature. It further describes that this production method can provide cerium oxide ultrafine particles with a high degree of uniformity in particle diameter and particle shape.
[0006] Furthermore, Non-Patent Document 1 discloses a method for producing ceria-coated silica that includes production steps similar to the method for producing cerium oxide ultrafine particles described in Patent Document 1. This method for producing ceria-coated silica does not include the firing-dispersion steps included in the production method described in Patent Document 1.
[0007] Patent Document 2 describes silica-based composite particles characterized by having a crystalline oxide layer B containing one or more elements selected from zirconium, titanium, iron, manganese, zinc, cerium, yttrium, calcium, magnesium, fluorine, lanthanum, and strontium on the surface of amorphous silica particles A. Furthermore, as a preferred embodiment, the document describes silica-based composite particles characterized by having an amorphous oxide layer C on the surface of amorphous silica particles A, which is an amorphous oxide layer containing an element such as aluminum and is different from the amorphous silica layer, and further having a crystalline oxide layer B thereon containing one or more elements selected from zirconium, titanium, iron, manganese, zinc, cerium, yttrium, calcium, magnesium, fluorine, lanthanum, and strontium. And, it is described that such silica-based composite particles have a crystalline oxide layer B on the surface of amorphous silica particles A, so that they can improve the polishing speed, and by pre-treating the silica particles, the sintering between particles during firing can be suppressed, and the dispersibility in the polishing slurry can be improved, and furthermore, they do not contain cerium oxide, or the amount of cerium oxide used can be significantly reduced, so that they can provide an inexpensive abrasive with high polishing performance.In addition, it is described that those that further have an amorphous oxide layer C between silica-based particles A and oxide layer B are particularly excellent in the effect of suppressing particle sintering and the effect of improving polishing speed.
[0008] Furthermore, Patent Document 3 describes a silica-based composite particle dispersion containing silica-based composite particles having an average particle size of 50 to 350 nm, wherein child particles mainly composed of crystalline ceria are disposed on the surface of mother particles mainly composed of amorphous silica, and the surfaces of the child particles are further coated with silica, and the dispersion has the following characteristics [1] to [3]: [1] The silica-based composite particles have a silica to ceria mass ratio of 100:11 to 316; [2] When the silica-based composite particles are subjected to X-ray diffraction, only the crystalline phase of ceria is detected; and [3] The silica-based composite particles have a crystallite size of 10 to 25 nm on the (111) plane of the crystalline ceria, as measured by X-ray diffraction. It is also stated that such silica-based composite microparticles can be used to polish even silica films, Si wafers, and other difficult-to-process materials at high speeds, while at the same time achieving high surface precision (low scratches, low surface roughness (Ra) of the substrate to be polished, etc.), and that because they do not contain impurities, a silica-based composite microparticle dispersion can be provided that can be preferably used to polish the surfaces of semiconductor devices such as semiconductor substrates and wiring boards. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] Patent No. 2,746,861 [Patent Document 2] Japanese Patent Application Laid-Open No. 2013-119131 [Patent Document 3] International Publication No. 2016 / 159167 Brochure [Non-patent literature]
[0010] [Non-Patent Document 1] Seung-Ho Lee, Zhenyu Lu, SVBabu and Egon Matijevic, "Chemical mechanical polishing of thermal oxide films using silica particles coated with ceria", Journal of Materials Research, Volume 17, Issue 10, 2002, pp2744-2749 Summary of the Invention [Problem to be solved by the invention]
[0011] However, when the present inventors actually produced and examined the cerium oxide ultrafine particles described in Patent Document 1, they found that the polishing rate was low and that defects were likely to occur on the surface of the polishing substrate (deterioration of surface accuracy, increased scratches, and residue of abrasive on the surface of the polishing substrate). The inventors believe that the main reason for this is that, compared to the method for producing ceria particles which includes a calcination step (calcination increases the crystallinity of the ceria particles), the method for producing cerium oxide ultrafine particles described in Patent Document 1 does not include a calcination step and simply involves crystallizing cerium oxide particles from a liquid phase (aqueous solution containing cerous nitrate), resulting in a relatively low crystallinity of the cerium oxide particles produced.Furthermore, because no calcination process is performed, the cerium oxide does not adhere to the base particles, and instead remains on the surface of the polishing substrate.
[0012] Furthermore, since the ceria-coated silica described in Non-Patent Document 1 is not fired, the actual polishing rate is thought to be low. Furthermore, since it is not bonded to the silica particles, it easily falls off, resulting in a decrease in the polishing rate, a lack of polishing stability, and concerns about particles remaining on the surface of the polishing substrate.
[0013] Furthermore, the present inventors have found that when polishing is performed using silica-based composite particles having an oxide layer C described in Patent Document 2, impurities such as aluminum may remain on the surface of the semiconductor device, which may adversely affect the semiconductor device. Furthermore, the ceria particles described in these documents are attached to the base particles, but are not firmly fixed, and therefore tend to fall off from the base particles. Furthermore, when polishing is performed using abrasive grains in which crystalline ceria particles are formed on spherical silica mother particles, as described in Patent Document 2, the removal rate of the silica film is high due to the chemical reaction that occurs simultaneously with the mechanical action of the ceria particles during polishing. However, under high pressure conditions, the ceria crystals may fall off, wear down, or collapse, reducing the contact area between the substrate and the ceria, which may result in a slow removal rate.
[0014] Furthermore, the silica-based composite microparticle dispersion described in Patent Document 3 is capable of exhibiting excellent polishing performance (polishing speed, high surface accuracy, etc.) in polishing applications. However, with the trend toward higher density and integration of semiconductor devices, there is a demand for abrasive dispersions that exhibit even better polishing performance for semiconductor substrates.
[0015] The present invention aims to solve the above-mentioned problems, that is, to provide a ceria-based composite microparticle dispersion that can polish even silica films, Si wafers, and other difficult-to-process materials at high speed and, if it does not contain impurities, can be preferably used for polishing the surfaces of semiconductor devices such as semiconductor substrates and wiring boards, a method for producing the same, and a polishing abrasive dispersion containing the ceria-based composite microparticle dispersion. [Means for solving the problem]
[0016] The present inventors have conducted extensive research to solve the above problems and have completed the present invention. The present invention includes the following (1) to (10). (1) A ceria-based composite particle dispersion containing ceria-based composite particles having the following characteristics [1] to [3]: [1] The ceria-based composite microparticles have a mother particle, a cerium-containing silica layer on the surface of the mother particle, and child particles dispersed inside the cerium-containing silica layer, the mother particle being mainly composed of amorphous silica, and the child particles being mainly composed of crystalline ceria. [2] The ceria-based composite fine particles satisfy the following requirements: 1) On the electron microscope photograph, there exists a circle inscribed with the image of the ceria-based composite fine particle, and further, the image of the ceria-based composite fine particle has the following relationship with respect to an arch-shaped figure X consisting of an arc on the circumference of the circle and a chord: (I) It is at least partially inscribed in the chord of the arcuate figure X. (II) It is inscribed in the point D on the arc that bisects the entire length of the arc of the arc-shaped figure X, and is at least partially inscribed in the arc curve on one side of the arc and the arc curve on the other side of the arc with the point D as the center. 2) The area of the arched figure X is 1.0 to 1.5 times the area of the image of the ceria-based composite fine particles, the chord length is 80 nm or more, and the arrow height is 40 nm or more. [3] The ceria-based composite fine particles have an average particle diameter of 50 to 350 nm as determined by image analysis. (2) The ceria-based composite microparticle dispersion according to (1) above, wherein the ceria-based composite microparticles are inscribed in at least 20% of the chord of the arcuate figure X on an electron micrograph. (3) The ceria-based composite microparticle dispersion liquid according to (1) or (2) above, wherein, in an electron microscope photograph, the ceria-based composite microparticles are at least partially inscribed in arcuate curves extending along the arc over a length of w / 6 (w: total length of the arc) on both sides of a dividing point D on the arc that bisects the total length of the arc, and are also at least partially inscribed in two arcuate curves connecting to both ends of the arcuate curve. (4) The ceria-based composite microparticle dispersion according to any one of (1) to (3) above, further comprising ceria-based composite microparticles having the following characteristic [4]: [4] The coefficient of variation of the particle size distribution of the child particles of the ceria-based composite fine particles is in the range of 15 to 50%. (5) The ceria-based composite microparticle dispersion according to any one of (1) to (4) above, wherein the proportion of the ceria-based composite microparticles to all particles in an electron micrograph is 5 to 20%. (6) A polishing abrasive dispersion containing the ceria-based composite fine particle dispersion according to (1) or (2) above. (7) The polishing abrasive dispersion according to (6) above, characterized in that it is used for planarizing a semiconductor substrate on which a silica film is formed. (8) A method for producing a ceria-based composite microparticle dispersion, comprising the following steps 1 and 2, and producing the ceria-based composite microparticle dispersion according to any one of the above steps (1) to (5): Step 1: A step of stirring a silica-based microparticle dispersion liquid in which silica microparticles satisfying the following conditions 1), 2), and 3) are dispersed in a solvent, and continuously or intermittently adding a metal salt of cerium thereto while maintaining the temperature at 0 to 20°C, the pH at 5.0 to 9.0, and the oxidation-reduction potential at 50 to 500 mV, to obtain a precursor particle dispersion liquid containing precursor particles. 1) On the electron microscope photograph, there is a circle in which the image of the silica fine particles is inscribed, and further, the image of the silica fine particles has the following relationship with respect to an arch-shaped figure Y consisting of an arc and a chord on the circumference of that circle: (I) At least partially inscribed in the chord of the arcuate figure Y. (II) It is inscribed in the point D on the arc that bisects the entire length of the arc of the arc-shaped figure Y, and is at least partially inscribed in the arc curve on one side of the arc and the arc curve on the other side of the arc with the point D as the center. 2) The area of the arched figure Y is 1.0 to 1.5 times the area of the image of the silica fine particles, the chord length is 80 nm or more, and the arrow height is 40 nm or more. 3) The silica fine particles have an average particle diameter of 50 to 350 nm as determined by image analysis. Step 2: A step of drying the precursor particle dispersion, calcining it at 850 to 1,100°C, adding a solvent to the resulting calcined body, and wet-crushing it in the pH range of 8.6 to 10.8 to obtain the ceria-based composite microparticle dispersion. (9) The method for producing a ceria-based composite microparticle dispersion according to (8) above, wherein the step 2 is a step of adding the solvent to the fired body, wet-crushing the body at a pH in the range of 8.6 to 10.8, followed by centrifuging the mixture at a relative centrifugal acceleration of 300 G or more, and then removing the precipitated components to obtain the ceria-based composite microparticle dispersion. (10) The method for producing a ceria-based composite microparticle dispersion according to (8) or (9), wherein the step 1 comprises adjusting a pH of a dispersion containing spherical silica particles to a range of 9.5 to 10.5 and wet-disintegrating the dispersion to obtain the silica microparticles. [Effects of the Invention]
[0017] Using a polishing abrasive dispersion containing the ceria-based composite microparticles of the present invention, it is possible to polish objects at high speeds. When the ceria-based composite microparticle dispersion of the present invention is used, for example, as a polishing abrasive dispersion for polishing difficult-to-process materials such as silica films or Si wafers, it is possible to polish objects at higher speeds than when using a conventional polishing abrasive dispersion (e.g., a polishing abrasive dispersion containing abrasives composed of spherical silica microparticles). While the reason for this is unclear, the inventors believe that the ceria-based composite microparticles of the present invention have a partially flat surface, which allows sliding friction to act on the surface being polished. This sliding friction on the surface being polished is thought to improve the polishing rate compared to abrasives that act through rolling friction. The method for producing a ceria-based composite microparticle dispersion of the present invention provides a method for efficiently producing a ceria-based composite microparticle dispersion that exhibits such excellent performance. In the method for producing a ceria-based composite fine particle dispersion of the present invention, it is possible to significantly reduce impurities contained in the ceria-based composite fine particles and achieve high purity. The highly purified ceria-based composite microparticle dispersion obtained by the preferred embodiment of the method for producing a ceria-based composite microparticle dispersion of the present invention does not contain impurities and is therefore particularly suitable for polishing the surfaces of semiconductor devices such as semiconductor substrates and wiring boards. Furthermore, when used as an abrasive dispersion for polishing, the ceria-based composite fine particle dispersion of the present invention is effective for planarizing the surface of a semiconductor device, and is particularly suitable for polishing a substrate on which a silica insulating film is formed. [Brief explanation of the drawings]
[0018] [Figure 1]1A and 1B are photographs and diagrams illustrating the shape of the composite fine particles of the present invention. [Figure 2] 1 is a schematic cross-sectional view of a composite fine particle of the present invention. [Figure 3] FIG. 3(a) is an SEM image (100,000 magnification) of the silica-based fine particles used in Example 1, and FIG. 3(b) is a TEM image (100,000 magnification). [Figure 4] 1 is an SEM image (100,000 magnifications) of the ceria-based composite fine particles obtained in Example 1. [Figure 5] 1 is an X-ray diffraction pattern of the ceria-based composite fine particles obtained in Example 1. [Figure 6] FIG. 6(a) is an SEM image (100,000 magnification) of the ceria-based composite fine particles obtained in Comparative Example 1, and FIG. 6(b) is a TEM image (100,000 magnification). DETAILED DESCRIPTION OF THE INVENTION
[0019] The present invention will now be described. The present invention provides a ceria-based composite microparticle dispersion containing ceria-based composite microparticles having the following characteristics [1] to [3]. [1] The ceria-based composite microparticles have a mother particle, a cerium-containing silica layer on the surface of the mother particle, and child particles dispersed inside the cerium-containing silica layer, the mother particle being mainly composed of amorphous silica, and the child particles being mainly composed of crystalline ceria. [2] The ceria-based composite fine particles satisfy the following requirements: 1) On the electron microscope photograph, there exists a circle in which the image of the ceria-based composite fine particle is inscribed, and further, the image of the ceria-based composite fine particle has the following relationship with respect to an arch-shaped figure X consisting of an arc on the circumference of the circle and a chord: (I) It is at least partially inscribed in the chord of the arcuate figure X. (II) It is inscribed in the point D on the arc that bisects the entire length of the arc of the arc-shaped figure X, and is at least partially inscribed in the arc curve on one side of the arc and the arc curve on the other side of the arc with the point D as the center. 2) The area of the arched figure X is 1.0 to 1.5 times the area of the image of the ceria-based composite fine particles, the chord length is 80 nm or more, and the arrow height is 40 nm or more. [3] The ceria-based composite fine particles have an average particle diameter of 50 to 350 nm as determined by image analysis. Such a ceria-based composite fine particle dispersion will be hereinafter referred to as the "dispersion of the present invention." Moreover, the ceria-based composite fine particles having the above characteristics [1] to [3] will also be referred to as "composite fine particles of the present invention" hereinafter.
[0020] The present invention also provides a method for producing a ceria-based composite fine particle dispersion, which method includes the following steps 1 and 2, and by which the dispersion of the present invention can be obtained. Step 1: A step of stirring a silica-based microparticle dispersion liquid in which silica microparticles satisfying the following conditions 1), 2), and 3) are dispersed in a solvent, and continuously or intermittently adding a metal salt of cerium thereto while maintaining the temperature at 0 to 20°C, the pH at 5.0 to 9.0, and the oxidation-reduction potential at 50 to 500 mV, to obtain a precursor particle dispersion liquid containing precursor particles. 1) On the electron microscope photograph, there is a circle in which the image of the silica fine particles is inscribed, and further, the image of the silica fine particles has the following relationship with respect to an arch-shaped figure Y consisting of an arc and a chord on the circumference of that circle: (I) At least partially inscribed in the chord of the arcuate figure Y. (II) It is inscribed in the point D on the arc that bisects the entire length of the arc of the arc-shaped figure Y, and is at least partially inscribed in the arc curve on one side of the arc and the arc curve on the other side of the arc with the point D as the center. 2) The area of the arched figure Y is 1.0 to 1.5 times the area of the image of the silica fine particles, the chord length is 80 nm or more, and the arrow height is 40 nm or more. 3) The silica fine particles have an average particle diameter of 50 to 350 nm as determined by image analysis. Step 2: A step of drying the precursor particle dispersion, calcining it at 850 to 1,100°C, adding a solvent to the resulting calcined body, and wet-crushing it in the pH range of 8.6 to 10.8 to obtain the ceria-based composite microparticle dispersion. Such a production method will be hereinafter referred to as the "production method of the present invention."
[0021] The dispersion of the present invention is preferably produced by the production method of the present invention.
[0022] Hereinafter, when simply referring to "the present invention", it means any of the dispersion of the present invention, the composite fine particles of the present invention, and the production method of the present invention.
[0023] In this specification, unless otherwise specified, the expression "image of ceria-based composite fine particles" means "electron microscope photograph of ceria-based composite fine particles." Electron micrographs refer to scanning electron micrographs (images) or transmission electron micrographs (images). Note that scanning electron micrographs (images) are sometimes abbreviated as "SEM" and transmission electron micrographs (images) as "TEM." Similarly, the expressions "image of silica-based fine particles" or "image of silica fine particles" mean "electron microscope photograph of silica-based fine particles" or "electron microscope photograph of silica fine particles," respectively. Furthermore, unless otherwise specified, the expression "ceria-based composite microparticles in an electron microscope photograph" means "in an electron microscope photograph of ceria-based composite microparticles." Similarly, the expression "silica-based microparticles in an electron microscope photograph" means "in an electron microscope photograph of silica-based microparticles," and the expression "silica microparticles in an electron microscope photograph" means "in an electron microscope photograph of silica microparticles."
[0024] <Composite fine particles of the present invention> The composite fine particles of the present invention are characterized by having a pseudo-spherical structure, as will be described later. The shape of the composite fine particles of the present invention will be explained with reference to FIG. Figure 1(a) is an SEM image of the composite microparticle of the present invention magnified 100,000 times. Figure 1(a) also shows a line for specifying an arcuate figure X inscribed in the composite microparticle of the present invention. Figure 1(b) shows the arcuate figure X specified by Figure 1(a). (a) 1: Composite particle 5: String 3: Circle (b) 7: Arc 9: Arrow height D: Point where arc 7 is divided 10: Bow shape X L1: Start point of arc 7 L2: End point of arc 7 S: A point on the arc 7, located on the L1 side from the dividing point D, equivalent to one-sixth of the total length (w) of the arc 7 T: A point on the arc 7, located on the L2 side from the dividing point D, equivalent to one-sixth of the total length (w) of the arc 7 ST: A circular curve on arc 7 that connects point S and point T
[0025] In this specification, all or part of the arc (from the start point L1 to the end point L2) that constitutes the portion of the arch-shaped figure other than the chord 5 may be referred to as an "arc curve."
[0026] 1(a), a method for specifying the arched figure X will be described. Note that the arched figure Y is also specified by the same method. First, an electron microscope photograph (SEM image in the case of FIG. 1) of the composite fine particle 1 of the present invention magnified 100,000 times is prepared. Then, for one composite particle on the image, a circle 3 is determined in which as much of the periphery of the composite particle as possible is inscribed. Next, a chord 5 is determined in which as much of the periphery of the image of the composite particle as possible is inscribed in the circle 3. By determining the circle 3 and the chord 5, an arch-shaped figure consisting of the chord 5 and an arc 7 is specified.
[0027] The specification of the arcuate figure X in the present invention will be described with reference to FIG. Using the method shown in FIG. 1(a), the circle 3 and chord 5 in which the image of the composite particle 1 is inscribed are determined. The two intersections of chord 5 and circle 3 are defined as start point L1 and end point L2, respectively, and the curve connecting start point L1 and end point L2 on the circumference is defined as arc 7. Here, an arc-shaped figure consisting of chord 5 and arc 7 is identified. Such an arch-shaped figure is selected, and in the relationship between the image of the composite particle 1 and the arch-shaped figure, the image of the composite particle 1 is inscribed in the dividing point D that divides the arc 7 equally, and is at least partially inscribed in both the arc curve (D-L1) extending from the dividing point D in the direction of the starting point L1 of the arc 7 and the arc curve (D-L2) extending from the dividing point D in the direction of the ending point L2 of the arc 7. The length of the arrow height 9 of the arch-shaped figure consisting of the arc 7 and the chord 5 and the area of the arch-shaped figure (area S X (Let us say) The length of the chord 5 is 80 nm or more, the length of the arrow height 9 is 40 nm or more, and the area of the arcuate shape is S X is 1.0 to 1.5 times (area S X / area S0), the arc shape consisting of the arc 7 and chord 5 is defined as arc shape X. When such an arched figure X is specified, the image of the corresponding composite particle is taken as the image of the composite particle 1 of the present invention.
[0028] In the present application, the shape of the composite microparticle 1 of the present invention is sometimes referred to as "pseudo-defective" and such particles are sometimes referred to as "pseudo-defective particles" or "pseudo-defective particles." In other words, composite microparticles that can specify the arcuate figure X are called pseudo-defective particles. In geometry, a three-dimensional structure obtained by cutting a sphere along one surface is sometimes called a "defective."
[0029] The composite microparticles of the present invention are those in which the arch-shaped figure X can be identified in their electron microscope photographs, and the image of the composite microparticles and the straight line portion inscribed by the chord 5 substantially correspond to the planar structure of the composite microparticles of the present invention. Such a planar structure is sometimes referred to as a "planar structure F." The composite particles of the present invention have such a pseudo-spherical structure, and when used as polishing abrasive grains in particular, the sliding friction effect is likely to be exerted, which is thought to contribute to an improvement in the polishing rate.
[0030] Here, the method for measuring the area S0 of the image of the composite fine particle 1 of the present invention on the electron microscope photograph is not particularly limited, and can be measured using, for example, a conventionally known image processing device.
[0031] Area S of the arc shape X X is 1.0 to 1.5 times the area S0 of the image of the composite particle 1 of the present invention, which has a pseudo-spherical shape. X / area S0) is preferably 1.0 to 1.3, and more preferably 1.0 to 1.1. Area S of the arc shape X X is in the range of 1.0 to 1.5 times the area S0 of the image of the composite microparticle 1 of the present invention, which has a pseudo-spherical shape, and satisfies other requirements (range of chord length, range of arrow height length, range of average particle diameter of the composite microparticle, and the requirements regarding inscription of (I) and (II) above), when used as an abrasive grain for polishing, sliding friction occurs easily with the substrate to be polished, which can contribute to improving the polishing rate.
[0032] The average particle size of the ceria-based composite fine particles of the present invention, as measured by image analysis, is preferably 50 to 350 nm. When the dispersion of the present invention is used as an abrasive, the occurrence of scratches during polishing is reduced. If the average particle size is less than 50 nm, the particle size is small and the polishing rate may not reach a practical level. Furthermore, if the average particle size exceeds 350 nm, it may result in a decrease in the surface precision of the substrate to be polished. The average particle size of the composite microparticles of the present invention is measured by the following image analysis method. An electron microscope photograph (transmission electron microscope photograph) of the composite microparticles of the present invention magnified 100,000 times is prepared, and for any 50 particles on the image, the maximum diameter of the particle is taken as the major axis, and its length is measured and defined as the major axis (DL). A point is determined on the major axis that divides the major axis into two equal parts, and two points where a line perpendicular to this intersects with the outer edge of the particle are found. The distance between these two points is measured and defined as the minor axis (DS). The geometric mean value of the major axis (DL) and minor axis (DS) is then calculated and defined as the particle size of the particle. In this way, the particle diameters of 50 particles are measured, and the value obtained by simply averaging these values is taken as the average particle diameter.
[0033] The arrow height 9 of the arched figure X corresponding to the composite microparticle 1 of the present invention is the distance between the chord 5 on a straight line that passes through the center of the circle 3 and is perpendicular to the chord 5 and the arc 7. Note that the arrow height value is necessarily determined to be unique for each arched figure. Such an arrow height 9 is preferably 40 nm or more in the arched figure X. The composite microparticles of the present invention that are inscribed in an arched figure having an arrow height of 40 nm or more in an electron micrograph have a sufficient thickness as abrasive grains, are not easily broken, and are suitable for polishing by sliding friction. In the case of composite particles that are inscribed in an arched shape with an arrow height of less than 40 nm in an electron micrograph, the composite particles may not be thick enough to be used as abrasive grains. More preferably, the composite microparticles of the present invention are inscribed in an arch shape with an arrow height of 50 nm or more on an electron micrograph. The upper limit of the arrow height is about 300 nm, corresponding to the average particle size range of the composite microparticles of the present invention (50 to 350 nm).
[0034] The chord 5 of the arched figure X corresponding to the composite microparticle 1 of the present invention is the line segment with the shortest distance connecting the starting point L1 and the ending point L2 of the circular arc curve of the arched figure X. The length of the chord 5 of the arcuate figure X corresponding to the composite particle 1 of the present invention is 80 nm or more. The length of the inscribed area of the image of the composite particle 1 of the present invention in the chord 5 is preferably 90 nm or more. The upper limit of the chord is about 430 nm, corresponding to the average particle size range of the composite fine particles of the present invention (50 to 350 nm).
[0035] In order to improve the polishing rate, friction caused by contact between particles and a substrate is important, and there are two types of dynamic friction: rolling friction and sliding friction, and it is generally believed that sliding friction generates a greater frictional force than rolling friction. The ceria-based composite fine particles of the present invention have a pseudo-spherical structure having at least one planar structure, and when used as polishing abrasive grains, the sliding friction effect is more likely to work, which is presumably responsible for improving the polishing rate compared to when spherical particles are used as polishing abrasive grains.
[0036] The composite fine particles of the present invention include the above-mentioned pseudo-spherical particles. For the composite microparticles of the present invention, an electron microscope photograph of the composite microparticles 1 of the present invention magnified 100,000 times is prepared using the method described above, and all particles in the image are judged as to whether they correspond to pseudo-defective particles in the same manner as described above. The number ratio of the pseudo-defective particles is then calculated. For such composite microparticles of the present invention, it is preferable that 5% or more of the particles are pseudo-defective particles, and this ratio is more preferably 7% or more. Furthermore, the number ratio may be 20% or less.
[0037] As described above, the composite fine particles of the present invention, which are an aggregate of a plurality of particles, mainly contain pseudo-spherical particles, but may also contain particles of other shapes. The image of the composite microparticle of the present invention is at least partially inscribed in the chord of the arcuate figure X, and it is desirable that it is inscribed in at least 20% of the chord of the arcuate figure X. This proportion is preferably 50% or more, more preferably 75% or more, and most preferably 100%. It is presumed that the higher the ratio of the image of the composite fine particle of the present invention to the inscribed chord, the wider the area of the planar structure F, and the more easily the sliding friction effect is exerted.
[0038] The image of the composite fine particle of the present invention is inscribed at a point D on the arc that bisects the entire length of the arc 7, and is at least partially inscribed in an arc curve (D-L1) on one side of the arc and an arc curve (D-L2) on the other side of the arc centered on the point D. More preferably, the image of the composite fine particle of the present invention is at least partially inscribed in an arc curve ST that extends over a length of (w) / 6 (w: total length of the arc) on both sides of the point D on the arc that bisects the entire length of the arc 7, and is also at least partially inscribed in two arc curves (S-L1, T-L1) that connect to both ends of the arc curve ST.
[0039] Next, the structure of the composite fine particles of the present invention will be explained with reference to FIG. Figures 2(a) and 2(b) are schematic diagrams illustrating cross sections of composite microparticles of the present invention. Figure 2(a) shows a type in which some of the child particles are exposed to the outside, while Figure 2(b) shows a buried type in which none of the child particles are exposed to the outside. As shown in Fig. 2, a composite microparticle 20 of the present invention has a mother particle 10, a cerium-containing silica layer 12 on the surface of the mother particle 10, and child particles 14 dispersed inside the cerium-containing silica layer 12. Note that the triangles in Fig. 2 are examples of measurement points X to Z where STEM-EDS analysis, which will be described later, is performed.
[0040] The present inventors have speculated as follows about the mechanism by which the cerium-containing silica layer is formed in the composite fine particles of the present invention and the mechanism by which the child particles are dispersed and present inside the cerium-containing silica layer.
[0041] 2, the mother particle 10, the cerium-containing silica layer 12, and the child particles 14 are clearly distinguished from each other for ease of understanding, but in reality, the composite microparticles of the present invention are integrated, and it is difficult to clearly distinguish between the mother particle 10, the cerium-containing silica layer 12, and the child particles 14 except by contrast in a STEM / SEM image or EDS analysis. However, when STEM-EDS analysis is performed on a cross section of the composite microparticles of the present invention and the element concentrations of Ce and Si are measured, it is possible to confirm that the structure shown in FIG. 2 is present.
[0042] Specifically, EDS analysis is performed by selectively irradiating an electron beam onto a location identified by a scanning transmission electron microscope (STEM). When the element concentrations of Ce and Si at measurement point X on the cross section of the composite microparticle of the present invention shown in FIG. 2 are measured, the ratio (percentage) of the Ce molar concentration to the sum of the Ce molar concentration and the Si molar concentration (Ce / (Ce+Si)×100) is less than 3%. Furthermore, when the element concentrations of Ce and Si at measurement point Z are measured, the ratio (percentage) of the Ce molar concentration to the sum of the Ce molar concentration and the Si molar concentration (Ce / (Ce+Si)×100) is greater than 50%. Furthermore, when the element concentrations of Ce and Si at measurement point Y are measured, the ratio (percentage) of the Ce molar concentration to the sum of the Ce molar concentration and the Si molar concentration (Ce / (Ce+Si)×100) is 3 to 50%. Therefore, in an elemental map obtained by STEM-EDS analysis, the mother particle 10 and the cerium-containing silica layer 12 in the composite microparticle of the present invention can be distinguished by a line where the ratio (percentage) of the Ce molar concentration to the sum of the Ce molar concentration and the Si molar concentration (Ce / (Ce+Si)×100) is 3%. Also, in an elemental map obtained by STEM-EDS analysis, the cerium-containing silica layer 12 and the daughter particle 14 in the composite microparticle of the present invention can be distinguished by a line where the ratio (percentage) of the Ce molar concentration to the sum of the Ce molar concentration and the Si molar concentration (Ce / (Ce+Si)×100) is 50%.
[0043] In this specification, STEM-EDS analysis is performed by observing at 800,000 magnifications.
[0044] Since the composite microparticles of the present invention have a configuration as shown in FIG. 2, when a cross section of the microparticles is subjected to STEM-EDS analysis and elemental mapping, it is often found that the microparticles have at least one layer with a relatively high ceria concentration (a layer made of ceria microparticles) between the outermost shell and the central mother particle (mainly composed of amorphous silica).
[0045] <Mother particle> The mother particles in the composite fine particles of the present invention will be described below. As described above, when STEM-EDS analysis is performed on the composite microparticles of the present invention and the element concentrations of Ce and Si are measured in the cross section of the composite microparticles of the present invention shown in Figure 2, the mother particle is the portion where the ratio (percentage) of the Ce molar concentration to the sum of the Ce molar concentration and the Si molar concentration (Ce / (Ce+Si) x 100) is less than 3%.
[0046] The average particle size of the base particles in the composite fine particles of the present invention is preferably 50 to 350 nm, more preferably 60 to 300 nm. When the dispersion of the present invention is used as an abrasive, the occurrence of scratches during polishing is reduced. If the average particle size of the base particles is less than 50 nm, the average particle size of the composite microparticles obtained using such base particles is unlikely to reach 50 nm, and when the dispersion of such composite microparticles is used as an abrasive, the polishing rate may not reach a practical level. Furthermore, when the average particle diameter of the base particles exceeds 350 nm, the average particle diameter of the composite microparticles obtained using such base particles often exceeds 350 nm. If a dispersion of such composite microparticles is used as an abrasive, the polishing rate may not reach a practical standard, and this may result in a decrease in the surface accuracy of the substrate being polished. It is more preferable that the base particles exhibit monodispersity.
[0047] The average particle size of the base particles in the composite fine particles of the present invention is measured as follows. An electron microscope photograph of the base particles of the composite microparticles of the present invention magnified 100,000 times is prepared, and for all particles in the image, the maximum diameter of the base particle is taken as the major axis, and its length is measured and defined as the major axis (DL). A point is determined on the major axis that divides the major axis in half, and two points where a line perpendicular to this intersects with the outer edge of the particle are found. The distance between these two points is measured and defined as the minor axis (DS). The geometric mean value of the major axis (DL) and the minor axis (DS) is then calculated and defined as the particle diameter of the base particle. In this way, the particle diameters of 50 mother particles are measured, and the value obtained by simply averaging these values is taken as the average particle diameter.
[0048] The shape of the base particles in the composite fine particles of the present invention is mainly a pseudo-trapezoidal particle. Specifically, the base particle is identified by observing at 800,000x magnification using STEM-EDS analysis and identifying the line where the ratio (percentage) of the Ce molar concentration to the sum of the Ce molar concentration and the Si molar concentration (Ce / (Ce+Si)×100) is 3%, and then it can be determined whether the base particle is pseudo-trapezoidal using a method similar to that used to determine whether the shape of the composite microparticles of the present invention described above is pseudo-trapezoidal.
[0049] The base particles are mainly composed of amorphous silica, and are usually silica fine particles or silica-based fine particles. These are preferably used because they are easy to prepare spherical particles with a uniform particle size and can also be prepared with a variety of particle sizes.
[0050] The fact that the base particles are mainly composed of amorphous silica can be confirmed, for example, by the following method. After drying a dispersion containing the composite microparticles of the present invention, the dispersion is pulverized in a mortar, and an X-ray diffraction pattern is obtained using, for example, a conventionally known X-ray diffractometer (e.g., RINT1400, manufactured by Rigaku Denki Co., Ltd.). No peaks of crystalline silica such as cristobalite appear. This confirms that the silica contained in the base particles is amorphous. In such cases, the base particles are considered to be mainly composed of amorphous silica. Furthermore, the dispersion of the present invention is dried, embedded in resin, and then sputter-coated with platinum. A cross-sectional sample is then prepared using a conventionally known focused ion beam (FIB) device. For example, when the prepared cross-sectional sample is subjected to fast Fourier transform (FFT) analysis using a conventionally known TEM device to obtain an FFT pattern, no diffraction pattern of crystalline silica such as cristobalite is observed. This confirms that the silica contained in the base particles is amorphous. In such cases, the base particles are considered to be primarily composed of amorphous silica. Another method is to use a conventionally known TEM device to observe the presence or absence of lattice fringes due to the atomic arrangement of the base particles on a cross-sectional sample prepared in the same manner. If the material is crystalline, lattice fringes corresponding to the crystalline structure are observed, while if the material is amorphous, lattice fringes are not observed. This confirms that the silica contained in the base particles is amorphous. In such cases, the base particles are considered to be composed primarily of amorphous silica.
[0051] The base particles are mainly composed of amorphous silica, and may contain 10 mass % or less of other elements such as La, Ce, and Zr, and may also contain crystalline silica and impurity elements. For example, it is desirable that the content of each of the elements Na, Ag, Al, Ca, Cr, Cu, Fe, K, Mg, Ni, Ti, Zn, and Zr (hereinafter sometimes referred to as "specific impurity group 1") in the base particles is 5000 ppm or less. Furthermore, the content of each of the elements U, Th, Cl, NO3, SO4 and F (hereinafter sometimes referred to as "specific impurity group 2") in the base particles is preferably 5 ppm or less.
[0052] Here, the content of specific impurities group 1 or specific impurities group 2 in the base particles, the composite fine particles of the present invention described below, and the silica fine particles described below means the content relative to the dry amount. The content relative to the dry amount refers to the ratio (percentage) of the weight of the object to be measured (specific impurity group 1 or specific impurity group 2) to the mass of the solid content contained in the object (base particles, composite microparticles of the present invention, or silica microparticles described below). Note that the impurity content of the base particles will generally match the impurity content of the silica microparticles if there is no contamination or other reasons.
[0053] <Child Particle> In the composite fine particles of the present invention, the child particles containing crystalline ceria as a main component (hereinafter also referred to as "ceria child particles") are dispersed in the cerium-containing silica layer disposed on the mother particle.
[0054] The ceria particles may be laminated in the cerium-containing silica layer, and the shape thereof may be spherical, elliptical, rectangular, or the like, but is not particularly limited. The particle size distribution may be uniform or sharp. Some of the ceria subparticles are embedded in the cerium-containing silica layer, while others are partially exposed from the cerium-containing silica layer.
[0055] As described above, when STEM-EDS analysis is performed on the composite microparticles of the present invention and the element concentrations of Ce and Si are measured in the cross section of the composite microparticles of the present invention shown in Figure 2, the child particles are those where the ratio (percentage) of the Ce molar concentration to the sum of the Ce molar concentration and the Si molar concentration (Ce / (Ce+Si) x 100) exceeds 50%.
[0056] The child particles of the present invention, which are primarily composed of crystalline ceria, are dispersed in a cerium-containing silica layer disposed on the mother particle. The coefficient of variation (CV) of the particle size distribution of the child particles is preferably 15 to 50%. That is, the child particles preferably have a wide particle size distribution. When the dispersion of the present invention, which contains ceria child particles with such a wide particle size distribution, is used as a polishing abrasive dispersion, the large child particles contact the substrate to be polished in the initial stage of polishing. Even if the child particles are dislodged, worn, or broken due to the polishing pressure, the small child particles subsequently contact the substrate, thereby maintaining a large contact area. This allows for efficient polishing at a stable polishing rate.
[0057] In the present invention, the coefficient of variation (CV value) in the particle size distribution of the child particles dispersed in the cerium-containing silica layer is preferably 15 to 50%, more preferably 16 to 35%, and even more preferably 18 to 30%.
[0058] The average particle size of the child particles is preferably 10 to 25 nm, and more preferably 14 to 23 nm. If the average particle size of the child particles exceeds 25 nm, the precursor particles containing such ceria child particles tend to sinter or aggregate after firing in step 2, making them difficult to disintegrate. Furthermore, such a ceria-based composite microparticle dispersion is undesirable for polishing purposes, as it can cause scratches on the polished object. Similarly, if the average particle size of the child particles is less than 10 nm, it tends to be difficult to achieve a practically sufficient polishing rate when used for polishing purposes.
[0059] Here, the particle size distribution of the child particles is measured as follows. First, the child particles are identified by observing at 800,000x magnification using STEM-EDS analysis, and the line at which the ratio (percentage) of the Ce molar concentration to the sum of the Ce molar concentration and the Si molar concentration (Ce / (Ce+Si) × 100) is 50% is identified. Next, the maximum diameter of the child particle is taken as the major axis, and its length is measured and this value is taken as the major diameter (DL). A point is also determined on the major axis that bisects the major axis, and two points where a line perpendicular to this intersects with the outer edge of the particle are found. The distance between these two points is measured and taken as the minor diameter (DS). The geometric mean of the major diameter (DL) and minor diameter (DS) is then calculated and this is taken as the particle diameter of the child particle. In this way, particle sizes of 100 or more child particles can be measured to obtain a particle size distribution.
[0060] The coefficient of variation (CV value) in the particle size distribution of the child particles is calculated by obtaining the standard deviation and the number average value using the particle size distribution obtained as described above as the population, dividing the standard deviation by the number average value, and multiplying the result by 100 (i.e., standard deviation / number average value × 100).
[0061] The child particles may be stacked within the cerium-containing silica layer, i.e., a plurality of child particles may be present within the cerium-containing silica layer on radial lines from the center of the mother particle. Furthermore, the child particles may be embedded in the cerium-containing silica layer or may be partially exposed to the outside of the cerium-containing silica layer. However, when the child particles are embedded in the cerium-containing silica layer, the surface of the ceria-based composite fine particle is closer to the silica surface, improving storage stability and polishing stability, and further reducing the amount of abrasive grains remaining on the substrate after polishing. Therefore, it is preferable that the child particles are embedded in the cerium-containing silica layer.
[0062] The shape of the child particles is not particularly limited. For example, they may be spherical, elliptical, or rectangular. When the dispersion of the present invention is used for polishing purposes and a high polishing rate is to be obtained, the child particles are preferably non-spherical, and more preferably rectangular.
[0063] The child particles dispersed in the cerium-containing silica layer disposed on the surface of the mother particle may be in a monodisperse state, in a layered state (i.e., a state in which multiple child particles are stacked in the thickness direction of the cerium-containing silica layer), or in a state in which multiple child particles are connected to each other.
[0064] In the present invention, the child particles are mainly composed of crystalline ceria. The fact that the child particles are mainly composed of crystalline ceria can be confirmed, for example, by drying the dispersion of the present invention, pulverizing the resulting solid in a mortar, or the like, to obtain the composite microparticles of the present invention, and then subjecting the composite microparticles to X-ray analysis using, for example, a conventionally known X-ray diffractometer (e.g., RINT1400, manufactured by Rigaku Corporation), and finding that only a crystalline phase of ceria is detected in the resulting X-ray diffraction pattern. In such cases, the child particles are considered to be mainly composed of crystalline ceria. The crystalline phase of ceria is not particularly limited, but examples thereof include cerianite.
[0065] The subparticles are mainly composed of crystalline ceria (crystalline Ce oxide), and may contain other elements, such as elements other than cerium, and may also contain a hydrous cerium compound as a polishing promoter. However, as described above, when the composite microparticles of the present invention are subjected to X-ray diffraction, only the crystalline phase of ceria is detected. That is, even if a crystalline phase other than ceria is contained, the content of the crystalline phase other than ceria is low or the crystalline phase is dissolved in the ceria crystal, so that the crystalline phase is outside the detection range by X-ray diffraction.
[0066] The average crystallite diameter of the ceria nanoparticles is calculated using the full width at half maximum of the maximum peak appearing in a chart obtained by subjecting the composite microparticles of the present invention to X-ray diffraction. For example, the average crystallite diameter of the (111) plane is 10 to 25 nm (full width at half maximum: 0.86 to 0.34°), preferably 14 to 23 nm (full width at half maximum: 0.62 to 0.37°). While the peak intensity of the (111) plane is often the greatest, the peak intensity of another crystal plane, such as the (100) plane, may also be the greatest. In this case, calculations can be made in the same way, and the average crystallite diameter in this case may be the same as the average crystallite diameter of the (111) plane.
[0067] The method for measuring the average crystallite size of the child particles is shown below using the (111) plane (near 2θ=28 degrees) as an example. First, the composite microparticles of the present invention are pulverized in a mortar, and an X-ray diffraction pattern is obtained using, for example, a conventionally known X-ray diffractometer (e.g., RINT1400 manufactured by Rigaku Denki Co., Ltd.). Then, the full width at half maximum of the peak of the (111) plane near 2θ=28 degrees in the obtained X-ray diffraction pattern is measured, and the average crystallite size can be calculated using the following Scherrer formula. D=Kλ / βcosθ D: average crystallite diameter (angstroms) K: Scherrer constant (in the present invention, K=0.94) λ: X-ray wavelength (1.5419 Å, Cu lamp) β: Full width at half maximum (rad) θ: reflection angle
[0068] In the composite fine particles of the present invention, it is preferable that silicon atoms are solid-dissolved in crystalline ceria which is the main component of the sub-particles. Generally, solid solution means that two or more kinds of elements (either metals or non-metals) are mutually dissolved and the whole becomes a uniform solid phase. Solid solutions obtained by solid solution are classified into substitution solid solutions and interstitial solid solutions. Substitution solid solutions can easily occur in atoms with similar atomic radii, but since Ce and Si have significantly different atomic radii, it is considered that at least substitution solid solutions are difficult to form. Also, in the crystal structure of cerianite, the coordination number of Ce as seen from the Ce center is 8, but for example, if Si substitutes for Ce on a one-to-one basis, the coordination number of Ce should be 7. However, in the analysis results of the preferred embodiment of the composite fine particles of the present invention, the average coordination number of Ce as seen from the Ce center is 8.0, and further, the average coordination number of Si is 1.2. Therefore, it is presumed that the preferred embodiment of the composite fine particles of the present invention is an interstitial type. Moreover, from the analysis results of the preferred embodiment of the composite fine particles of the present invention, since the interatomic distance between Ce and Si is smaller than the interatomic distance between Ce and Ce, the preferred embodiment of the composite fine particles of the present invention is presumed to be an interstitial solid solution. That is, regarding the cerium atoms and silicon atoms contained in the sub-particles, it is preferable to satisfy the relationship of R1 < R2 when the interatomic distance between cerium and silicon is R1 and the interatomic distance between cerium and cerium is R2.
[0069] Conventionally, when polishing a substrate with a silica film or a glass substrate using ceria particles as abrasive grains, it has been known that a particularly high polishing rate is exhibited compared to the case of using other inorganic oxide particles. As one of the reasons why ceria particles exhibit a particularly high polishing rate with respect to a substrate with a silica film, it has been pointed out that trivalent cerium contained in the ceria particles has high chemical reactivity with the silica film on the polished substrate.
[0070] In a preferred embodiment of the composite microparticles of the present invention, Si atoms are believed to form an interstitial solid solution in the CeO2 crystals of the child particles (ceria microparticles) present on the outer surface. The solid solution of Si atoms causes crystal distortion in the CeO2 crystals, resulting in increased oxygen vacancies even when fired at high temperatures, resulting in the production of large amounts of trivalent cerium, which is chemically active with SiO2. This enhances the chemical reactivity of CeO2, presumably resulting in the high polishing rate described above. Furthermore, doping with elements such as La or Zr may be used to increase the trivalent cerium content.
[0071] <Cerium-containing silica layer> The composite fine particles of the present invention have a cerium-containing silica layer on the surface of the mother particle, and the daughter particles are dispersed inside the cerium-containing silica layer.
[0072] By adopting such a structure, the child particles are less likely to fall off due to the crushing process during production or the pressure during polishing, and even if some child particles are chipped off, most of the child particles remain in the cerium-containing silica layer without falling off, so the polishing function is not reduced.
[0073] As described above, when STEM-EDS analysis is performed on the composite microparticles of the present invention to measure the element concentrations of Ce and Si in the cross section of the composite microparticles of the present invention, the cerium-containing silica layer is the portion where the ratio (percentage) of the Ce molar concentration to the sum of the Ce molar concentration and the Si molar concentration (Ce / (Ce+Si)×100) is 3 to 50%.
[0074] In an image (TEM image) obtained by observing the composite microparticles of the present invention using a transmission electron microscope, the images of the child particles appear thick on the surface of the mother particle, but also a portion of the cerium-containing silica layer appears as a relatively faint image around and outside the child particles, i.e., on the surface side of the composite microparticles of the present invention. STEM-EDS analysis of this portion reveals that the Si molar concentration and Ce molar concentration of the portion are very high. Specifically, the ratio (percentage) of the Ce molar concentration to the sum of the Ce molar concentration and the Si molar concentration (Ce / (Ce+Si)×100) is 3 to 50%.
[0075] The average thickness of the cerium-containing silica layer is not particularly limited, but is preferably 10 to 40 nm, more preferably 12 to 30 nm. As will be described later, it is acceptable if there are areas where the cerium-containing silica layer is not present. The average thickness of the cerium-containing silica layer is determined by drawing straight lines at any 12 points from the center of the base particle of the composite microparticle of the present invention to the outermost shell, measuring the distance between the line where the ratio (percentage) of the Ce molar concentration to the sum of the Ce molar concentration and the Si molar concentration (Ce / (Ce+Si)×100) is 3%, as determined from the element map obtained by the STEM-EDS analysis as described above, and the outermost shell of the composite microparticle of the present invention (the distance on the line passing through the center of the base particle), and then simply averaging these distances. Note that the center of the base particle refers to the intersection of the major axis and the minor axis.
[0076] The cerium-containing silica layer in the composite microparticles of the present invention is believed to enhance the bonding strength between the mother particles and the child particles (ceria microparticles composed primarily of crystalline ceria) that disperse and grow in the cerium-containing silica layer during the calcination process. Therefore, for example, in the process of obtaining the dispersion of the present invention, the calcined powder dispersion obtained by calcination may be pre-crushed by dry crushing if necessary, followed by wet crushing, and then centrifuged as necessary to obtain a ceria-based composite microparticle dispersion. The cerium-containing silica layer is believed to prevent the child particles from detaching from the mother particles. In this case, localized child particle shedding is not a problem, and it is not necessary for the entire surface of the child particles to be partially covered with the cerium-containing silica layer. It is sufficient for the child particles to be strong enough to prevent them from detaching from the mother particles during the crushing process. Due to this structure, when the dispersion of the present invention is used as an abrasive, it is believed that the polishing rate is high and deterioration of surface precision and scratches are minimal.
[0077] Furthermore, in the composite fine particles of the present invention, at least a portion of the surface of the child particles is covered with a cerium-containing silica layer, and therefore, -OH groups of silica are present on the outermost surface (outermost shell) of the composite fine particles of the present invention. Therefore, when used as an abrasive, the composite fine particles of the present invention repel each other due to the charges of the -OH groups on the surface of the polishing substrate, which is thought to result in reduced adhesion to the surface of the polishing substrate.
[0078] In general, ceria has a different potential from silica, polishing substrates, and polishing pads. As the pH approaches neutrality from alkaline, its negative zeta potential decreases, while in the weakly acidic range, it has a positive potential. Therefore, at acidic pH during polishing, ceria adheres to the polishing substrate or polishing pad due to differences in potential magnitude and polarity, and is prone to remain on the polishing substrate or polishing pad. On the other hand, the composite microparticles of the present invention, as described above, have silica in their outermost shells, which results in a negative charge due to silica, maintaining a negative potential from alkaline to acidic pH. As a result, abrasive particles are less likely to remain on the polishing substrate or polishing pad. When the disintegration treatment in step 2 of the manufacturing method of the present invention is performed while maintaining a pH of 8.6 to 10.8, a portion of the silica on the surface of the composite microparticles of the present invention (silica in the cerium-containing silica layer) dissolves. When the dispersion of the present invention produced under these conditions is adjusted to a pH of <7 for polishing applications, the dissolved silica deposits on the composite microparticles (abrasive grains) of the present invention, resulting in a negative surface potential of the composite microparticles of the present invention. When the potential is low, silicic acid may be added to adequately reinforce the cerium-containing silica layer.
[0079] Other properties of the composite fine particles of the present invention will be described below. In the composite fine particles of the present invention, the mass ratio of silica to ceria in the ceria-based composite fine particles is typically 100:11-316.
[0080] In the composite microparticles of the present invention, the mass ratio of silica (SiO2) to ceria (CeO2) is not limited as long as the composite microparticles exhibit useful polishing speed and surface precision when used as polishing abrasive grains, but is typically 100:11 to 316, preferably 100:30 to 316, more preferably 100:30 to 230, more preferably 100:30 to 150, more preferably 100:60 to 316, and even more preferably 100:60 to 230. The mass ratio of silica to ceria is generally considered to be approximately the same as the mass ratio of mother particles to daughter particles. If the amount of daughter particles relative to mother particles is too small, the mother particles or composite fine particles may bond together, resulting in the generation of coarse particles. In this case, an abrasive (polishing slurry) containing the dispersion of the present invention may cause defects (deterioration of surface accuracy, such as increased scratches) on the surface of the polishing substrate. Furthermore, if the amount of ceria relative to silica is too high, not only will the cost increase, but resource risks will also increase. Furthermore, fusion between particles will progress. As a result, the roughness of the substrate surface will increase (deterioration of surface roughness Ra), scratches will increase, and free ceria will remain on the substrate and may easily cause problems such as adhesion to the waste water pipes of the polishing device.
[0081] The silica to be calculated for the mass ratio of silica (SiO2) to ceria (CeO2) refers to all silica (SiO2) contained in the composite microparticles of the present invention, and therefore refers to the total amount of silica components constituting the mother particles, silica components contained in the cerium-containing silica layer disposed on the surface of the mother particles, and silica components that may be contained in the child particles.
[0082] The content (mass %) of silica (SiO2) and ceria (CeO2) in the composite fine particles of the present invention is determined by first determining the solids concentration of the dispersion of the present invention by subjecting it to ignition loss at 1000°C and weighing it. Next, the content (mass%) of cerium (Ce) contained in a predetermined amount of the composite microparticles of the present invention is determined by ICP plasma emission spectrometry and converted into oxide mass% (CeO2 mass% etc.). Then, assuming that the components other than CeO2 constituting the composite microparticles of the present invention are SiO2, the SiO2 mass% can be calculated. In the production method of the present invention, the mass ratio of silica to ceria can also be calculated from the amounts of the silica source material and the ceria source material used when preparing the dispersion of the present invention. This is applicable when the process is not one in which ceria or silica is dissolved and removed, and in such cases, the amounts of ceria or silica used and the analytical values show good agreement.
[0083] The number of coarse particles of 0.51 μm or more that can be contained in the dispersion of the present invention is preferably 100 million particles / cc or less in dry terms. The number of coarse particles is preferably 100 million particles / cc or less, and more preferably 80 million particles / cc or less. Coarse particles of 0.51 μm or more can cause polishing scratches and can also cause the surface roughness of the polished substrate to deteriorate.
[0084] The method for measuring the number of coarse particles that may be contained in the dispersion of the present invention is as follows. After diluting the sample with pure water to 0.1% by mass, 5 ml of the sample was taken and injected into a conventional coarse particle number measuring device. The number of coarse particles of 0.51 μm or larger was then determined. This measurement was carried out three times, and the simple average value was calculated. This value was then multiplied by 1000 to obtain the number of coarse particles of 0.51 μm or larger.
[0085] The composite particles of the present invention are not particularly limited, but preferably have a specific surface area of 9 to 60 m 2 / g, and 10 to 43 m 2 / g is more preferred.
[0086] Here, a method for measuring the specific surface area (BET specific surface area) will be described. First, a dried sample (0.2 g) is placed in a measurement cell and degassed in a nitrogen gas stream at 250°C for 40 minutes. The sample is then kept at liquid nitrogen temperature in a mixed gas stream of 30% by volume nitrogen and 70% by volume helium, allowing the nitrogen to adsorb to the sample at equilibrium. Next, the temperature of the sample is gradually raised to room temperature while the mixed gas is being passed through. The amount of nitrogen desorbed during this process is measured, and the specific surface area of the sample is measured using a previously prepared calibration curve. Such a BET specific surface area measurement method (nitrogen adsorption method) can be carried out using, for example, a conventionally known surface area measurement device. In the present invention, the specific surface area means a value obtained by measurement using such a method, unless otherwise specified.
[0087] In the composite fine particles of the present invention, the content of each element of the specific impurity group 1 is preferably 100 ppm or less, more preferably 50 ppm or less, even more preferably 25 ppm or less, still more preferably 5 ppm or less, and even more preferably 1 ppm or less. Furthermore, the content of each element of specific impurity group 2 in the composite fine particles of the present invention is preferably 5 ppm or less. The method for reducing the content of each element of specific impurity group 1 and specific impurity group 2 in the composite fine particles of the present invention is as described above. The content of each element of the specific impurity group 1 and the specific impurity group 2 in the composite fine particles of the present invention can be measured by the following method. Na and K: Atomic absorption spectroscopy Ag, Al, Ca, Cr, Cu, Fe, Mg, Ni, Ti, Zn, Zr, U and Th: ICP-MS (Inductively Coupled Plasma Atomic Emission Spectroscopy Mass Analysis) ·Cl: Potentiometric titration method NO3, SO4 and F: Ion chromatograph
[0088] <Dispersion of the Present Invention> The dispersion of the present invention will now be described. The dispersion of the present invention is one in which the composite fine particles of the present invention as described above are dispersed in a dispersion solvent.
[0089] The dispersion of the present invention contains water and / or an organic solvent as a dispersion solvent. It is preferable to use water, such as pure water, ultrapure water, or ion-exchanged water, as the dispersion solvent. Furthermore, the dispersion of the present invention can be suitably used as a polishing slurry by adding one or more additives selected from the group consisting of a polishing accelerator, a surfactant, a pH adjuster, and a pH buffer to control the polishing performance.
[0090] In addition, examples of the dispersion solvent that can be used in the dispersion of the present invention include organic solvents such as alcohols such as methanol and ethanol; amides such as acetone and 2-butanone; ethers such as diethyl ether and isopropyl ether; glycol ethers such as 2-methoxyethanol and 2-ethoxyethanol; glycol ether acetates such as 2-methoxyethyl acetate and 2-ethoxyethyl acetate; esters such as methyl acetate and ethyl acetate; aromatic hydrocarbons such as benzene, toluene, and xylene; aliphatic hydrocarbons such as hexane and heptane; halogenated hydrocarbons such as methylene chloride, 1,2-dichloroethane, dichloropropane, and chlorobenzene; sulfoxides such as dimethyl sulfoxide; and pyrrolidones such as N-methyl-2-pyrrolidone and N-octyl-2-pyrrolidone. These may also be mixed with water.
[0091] The solid content concentration in the dispersion of the present invention is preferably in the range of 0.3 to 50% by mass.
[0092] <Production Method of the Present Invention> The manufacturing method of the present invention will be described. The manufacturing method of the present invention comprises steps 1 and 2 described below.
[0093] <Process 1> In step 1, a silica-based fine particle dispersion liquid in which silica fine particles are dispersed in a solvent is prepared. In this specification, "Step 1" may also be referred to as "blending step."
[0094] The silica-based fine particle dispersion liquid used as a raw material in step 1 is a silica-based fine particle dispersion liquid in which silica fine particles satisfying the following conditions 1), 2) and 3) are dispersed in a solvent. 1) On the electron microscope photograph, there is a circle in which the image of the silica fine particles is inscribed, and further, the image of the silica fine particles has the following relationship with respect to an arch-shaped figure Y consisting of an arc and a chord on the circumference of that circle: (I) At least partially inscribed in the chord of the arcuate figure Y. (II) It is inscribed in the point D on the arc that bisects the entire length of the arc of the arc-shaped figure Y, and is at least partially inscribed in the arc curve on one side of the arc and the arc curve on the other side of the arc with the point D as the center. 2) The area of the arched figure Y is 1.0 to 1.5 times the area of the image of the silica fine particles, the chord length is 80 nm or more, and the arrow height is 40 nm or more. 3) The silica fine particles have an average particle diameter of 50 to 350 nm as determined by image analysis.
[0095] Here, the arched figure Y is defined in the same manner as the arched figure X. The preferred range of the area of the arched figure Y relative to the area of the image of the silica fine particles is also the same as that of the arched figure X. Furthermore, the preferred ranges of the chord length and arrow height of the arched figure Y are also the same as those of the arched figure X. Furthermore, the average particle size of the silica fine particles is a value obtained by measuring using the same method as the average particle size of the composite fine particles of the present invention described above.
[0096] The silica-based microparticle dispersion liquid used as the raw material may contain not only pseudo-spherical silica microparticles but also other silica microparticles. The proportion of the pseudo-spherical silica microparticles is not particularly limited, but is usually desirably 5 to 20 mass % in terms of number proportion.
[0097] A silica-based microparticle dispersion containing pseudo-spherical silica microparticles can be obtained, for example, by subjecting a silica-based microparticle dispersion containing known spherical silica microparticles to a wet crushing treatment in the pH range of 9.5 to 10.5.
[0098] The silica microparticles in the silica-based microparticle dispersion used as a raw material in step 1 may have an average particle size equivalent to that of the ceria-based composite microparticles in the ceria-based composite microparticle dispersion obtained by the production method of the present invention, but are not particularly limited as long as the composite microparticles of the present invention having the desired average particle size can be obtained.
[0099] When preparing the dispersion of the present invention for use in polishing semiconductor devices, etc., by the manufacturing method of the present invention, it is preferable to use a silica-based particle dispersion in which silica particles prepared by hydrolysis of alkoxysilane are dispersed in a solvent.In addition, when using other conventionally known silica-based particle dispersions (such as silica-based particle dispersions prepared using water glass as a raw material), it is preferable to acid-treat the silica-based particle dispersion and then deionize it before use.In this case, the content of Na, Ag, Al, Ca, Cr, Cu, Fe, K, Mg, Ni, Ti, Zn, U, Th, Cl, NO3, SO4 and F contained in the silica particles is reduced, specifically, can be 100 ppm or less. Specifically, silica fine particles in the silica-based fine particle dispersion liquid, which is the raw material, that satisfy the following conditions (a) and (b) are preferably used. (a) The content of Na, Ag, Al, Ca, Cr, Cu, Fe, K, Mg, Ni, Ti and Zn is 100 ppm or less. (b) The content of U, Th, Cl, NO3, SO4 and F is each 5 ppm or less. The method for measuring the content of each of the components (a) and (b) that may be contained in the silica microparticles may be the same as the method for measuring the content of each element in specific impurity group 1 and specific impurity group 2 that may be contained in the composite microparticles of the present invention.
[0100] In addition, silica microparticles with an appropriate reactivity with cerium (dissolved weight of silica microparticles per weight of ceria) are preferably used. In the preparation step (step 1) of the manufacturing method of the present invention, a metal salt of cerium is added to a silica-based microparticle dispersion, whereby a portion of the silica is dissolved by cerium hydroxide or the like, reducing the size of the silica microparticles and forming a precursor of a cerium-containing silica layer containing cerium microcrystals on the surface of the dissolved silica microparticles. If the silica microparticles are made of amorphous silica with high reactivity with cerium, the precursor of the cerium-containing silica layer will become thick, and the cerium-containing silica layer formed by firing will become thick or the silica content of the layer will become excessively high, making it difficult to disintegrate in the disintegration step. Furthermore, if the silica microparticles are made of amorphous silica with extremely low reactivity with cerium, the cerium-containing silica layer will not be sufficiently formed, and the ceria subparticles will be prone to falling off. When the reactivity with cerium is appropriate, the dissolution of excess silica is suppressed, the cerium-containing silica layer has an appropriate thickness, which prevents the child particles from falling off, and its strength is thought to be greater than the strength between the composite fine particles, making it easy to crush, which is desirable.
[0101] In step 1, a silica-based microparticle dispersion liquid in which silica microparticles are dispersed in a solvent is stirred, and a metal salt of cerium is added continuously or intermittently while maintaining the temperature at 0 to 20°C, the pH range at 5.0 to 9.0, and the redox potential at 50 to 500 mV, thereby neutralizing the metal salt of cerium and obtaining a precursor particle dispersion liquid containing precursor particles.
[0102] The dispersion medium in the silica-based fine particle dispersion preferably contains water, and it is preferable to use an aqueous silica-based fine particle dispersion (aqueous sol).
[0103] The solid content concentration in the silica-based fine particle dispersion is preferably 1 to 40 mass % in terms of SiO2 If this solid content concentration is too low, the silica concentration in the production process will be low, which may result in poor productivity.
[0104] In the manufacturing method of the present invention, for example, if the reaction temperature between silica fine particles and a metal salt of cerium in step 1 is set to 40 to 50°C, the reactivity between ceria and silica increases, and dissolution of the silica fine particles progresses. As a result, the particle size of the CeO2 ultrafine particles in the precursor particles obtained by drying in the intermediate stage of step 2 is less than 2.5 nm. This indicates that if silica reacts with ceria in the liquid phase at such a high temperature range, the silica inhibits the particle growth of ceria, and the average particle size of the ceria after drying becomes small, less than 2.5 nm. Even with such precursor particles, it is possible to increase the average crystallite diameter of the ceria particle particles to 10 nm or more by firing at a temperature above 1100 °C. However, in this case, a silica coating is formed instead of a cerium-containing silica layer. This silica coating tends to tightly coat the ceria particle, making it difficult to crush. Therefore, by maintaining the reaction temperature at 0 to 20 °C and appropriately suppressing the reaction between silica and ceria in the liquid phase, the average crystallite diameter of the CeO2 ultrafine particles in the dried precursor particles can be increased to 2.5 nm or more, resulting in particles that are easy to crush. Furthermore, because the average crystallite diameter after drying is large, the firing temperature can be lowered to increase the average crystallite diameter of the ceria particle particles to 10 nm or more. This prevents the cerium-containing silica layer formed by firing from becoming excessively thick, making crushing easier.
[0105] Furthermore, impurities can be extracted using a cation exchange resin or anion exchange resin, or a mineral acid, an organic acid, or the like, and the silica-based microparticle dispersion can be deionized, if necessary, using an ultrafiltration membrane, etc. Silica-based microparticle dispersions from which impurity ions have been removed by deionization treatment are more preferred because they facilitate the formation of silicon-containing hydroxides on the surface. However, deionization treatments are not limited to these.
[0106] In the production method of the present invention, for example, if the oxidation-reduction potential during the reaction between the silica fine particles and the metal salt of cerium in step 1 is low, rod-shaped crystals are generated, which are difficult to deposit on the silica fine particles. Furthermore, if the redox potential is not adjusted within the specified range, the CeO2 ultrafine particles produced in the blending process tend not to crystallize easily, and the crystallization of uncrystallized CeO2 ultrafine particles is not promoted even by heating and aging after blending. Therefore, in order to crystallize to the specified size in the firing process in step 2, firing at a high temperature is required, making disintegration difficult.
[0107] The type of cerium metal salt is not limited, but cerium chloride, nitrate, sulfate, acetate, carbonate, metal alkoxide, etc. can be used. Specific examples include cerium (I) nitrate, cerium carbonate, cerium (I) sulfate, and cerium (I) chloride. Among these, trivalent cerium salts such as cerium (I) nitrate, cerium (I) chloride, and cerium carbonate are preferred. Upon neutralization, the supersaturated solution generates crystalline cerium oxide and cerium hydroxide, which rapidly aggregate and deposit on silica particles, ultimately forming monodispersed ultrafine CeO particles. Furthermore, trivalent cerium salts react moderately with silica particles, facilitating the formation of a cerium-containing silica layer. Furthermore, trivalent cerium, which is highly reactive with the silica film formed on the polishing substrate, is preferred because it easily forms in ceria crystals. However, sulfate ions, chloride ions, nitrate ions, etc. contained in these metal salts are corrosive. Therefore, if desired, they may need to be removed to below 5 ppm by post-processing after preparation. On the other hand, carbonates are preferably used because they are released as carbon dioxide gas during preparation, and alkoxides are decomposed into alcohols.
[0108] The amount of cerium metal salt added to the silica-based microparticle dispersion is preferably an amount such that the mass ratio of silica to ceria in the resulting ceria-based composite microparticles is in the range of 100:11 to 316, as in the case of the composite microparticles of the present invention described above.
[0109] Before or after adding a cerium metal salt to a silica-based microparticle dispersion, the stirring temperature is preferably 0 to 20°C, more preferably 3 to 20°C, and even more preferably 3 to 18°C. If this temperature is too low, the reactivity between ceria and silica decreases, significantly reducing the solubility of silica, resulting in uncontrolled ceria crystallization. As a result, coarse ceria crystalline oxides are formed, causing abnormal growth of CeO2 ultrafine particles on the surface of the silica microparticles, making them difficult to disintegrate after firing. Furthermore, the amount of silica dissolved by the cerium compound is reduced, resulting in a decrease in the amount of silica supplied to the cerium-containing silica layer. This may result in a shortage of silica, which acts as a binder between the silica mother particles and the ceria child particles (insufficient silica to be layered on the mother particles), making it difficult for the ceria child particles to be fixed to the silica mother particles. Conversely, if the temperature is too high, the solubility of silica will increase significantly, which may inhibit the formation of crystalline ceria oxide. However, the high temperature required during firing may promote interparticle bonding, making it impossible to disintegrate the particles. Furthermore, this is undesirable because it may lead to the formation of scale on the reactor walls. Furthermore, silica fine particles that are difficult to dissolve in cerium compounds (neutralized cerium salts) are preferred. In the case of easily soluble silica fine particles, the silica inhibits the crystal growth of ceria, resulting in a particle size of less than 2.5 nm for the CeO2 ultrafine particles during the compounding stage. If the particle size of the CeO2 ultrafine particles at the preparation stage is less than 2.5 nm, the firing temperature must be high to make the ceria particle size 10 nm or more after firing, in which case the cerium-containing silica layer may tightly coat the base particles, making them difficult to disintegrate.The solubility of easily soluble silica fine particles can be reduced by drying them at 100°C or higher before using them as a raw material. Furthermore, in step 1, by adding a metal salt of cerium to the silica-based microparticle dispersion and then stirring at a temperature of 0 to 20°C, it is possible to obtain the dispersion of the present invention containing the composite microparticles of the present invention, in which the coefficient of variation in the particle size distribution of the child particles is at an appropriate value.
[0110] Furthermore, after adding the cerium metal salt to the silica-based particle dispersion, the stirring time is preferably 0.5 to 50 hours, more preferably 0.5 to 35 hours. If this time is too short, the CeO2 ultrafine particles tend to aggregate, making it difficult to react with silica on the surface of the silica particles, and forming composite particles that are difficult to disintegrate, which is undesirable. Conversely, if this time is too long, the reaction to form the CeO2 ultrafine particle-containing layer will not proceed any further, which is uneconomical. After adding the cerium metal salt, the mixture may be aged at 0 to 80°C if desired. This is because aging promotes the reaction of the cerium compound and also has the effect of adhering free CeO2 ultrafine particles that are not attached to the silica particles to the silica particles.
[0111] Furthermore, before or after adding the metal salt of cerium to the silica-based microparticle dispersion, the pH range of the silica-based microparticle dispersion during stirring is 5.0 to 9.0, preferably 7.6 to 9.0. In this case, it is preferable to adjust the pH by adding an alkali or the like. Examples of such alkali include known alkalis. Specific examples include, but are not limited to, aqueous ammonia solution, alkali hydroxide, alkaline earth metal, and aqueous amine solutions.
[0112] Furthermore, before or after adding the cerium metal salt to the silica-based particle dispersion, the oxidation-reduction potential of the particle dispersion is adjusted to 50 to 500 mV during stirring. The oxidation-reduction potential is preferably 100 to 300 mV. This is because the acid-reduction potential of the particle dispersion decreases during mixing when trivalent cerium metal salt is used as a raw material. Maintaining the oxidation-reduction potential within this range also promotes crystallization of the resulting CeO2 ultrafine particles. If the oxidation-reduction potential is below 50 mV or becomes negative, the cerium compound may not deposit on the surface of the silica particles, resulting in the formation of plate-like or rod-like ceria particles or composite ceria particles. Furthermore, the reactivity of cerium hydroxide and other elements with the silica particles decreases, preventing the formation of a CeO2 ultrafine particle-containing layer. Even if a CeO2 ultrafine particle layer is formed, the silica content in the CeO2 ultrafine particle layer will be extremely low. As a result, a cerium-containing silica layer containing ceria subparticles is not formed after calcination, and the ceria subparticles tend to be exposed and arranged on the surface of the silica base particles. Methods for maintaining the redox potential within the above range include adding an oxidizing agent such as hydrogen peroxide, or blowing in air, oxygen, or ozone. If these methods are not used, the redox potential tends to be negative or below 50 mV.
[0113] Step 1 produces a dispersion (precursor particle dispersion) containing particles (precursor particles) that are precursors of the composite microparticles of the present invention. This step makes it possible to obtain CeO2 ultrafine particles contained in the precursor particles with an average crystallite diameter of 2.5 nm or more and less than 10 nm. If the reactivity between silica and ceria is too high, the average crystallite diameter of the CeO2 ultrafine particles contained in the precursor particles tends to be less than 2.5 nm, and therefore, in Step 2, firing at an excessively high temperature is required to obtain ceria particles with a diameter of 10 nm or more. As a result, the adhesion between the particles becomes strong, which may make crushing difficult.
[0114] As described above, in step 1, the silica-based fine particle dispersion is stirred and the cerium metal salt is added continuously or intermittently while maintaining the temperature at 0 to 20°C, the pH at 5.0 to 9.0, and the redox potential at 50 to 500 mV. It is preferable to then add the cerium metal salt continuously or intermittently while maintaining the temperature at higher than 20°C and not higher than 98°C, the pH at 5.0 to 9.0, and the redox potential at 50 to 500 mV, thereby obtaining the precursor particle dispersion. That is, in step 1, the treatment is carried out at a temperature of 0 to 20° C., but it is preferable to subsequently change the temperature to more than 20° C. and 98° C. or less to carry out the treatment, thereby obtaining the precursor particle dispersion liquid. This is because, by carrying out step 1 in this manner, it is easier to obtain the dispersion of the present invention containing the composite fine particles of the present invention in which the coefficient of variation in the particle size distribution of the child particles is at a suitable value. When treating at a temperature higher than 20°C and not higher than 98°C, the preferred values and adjustment methods for pH and oxidation-reduction potential are the same as when treating at a temperature of 0 to 20°C.
[0115] Conversely, the precursor particle dispersion may be obtained by treating the dispersion at a temperature higher than 20° C. and not higher than 98° C. before treating the dispersion at a temperature of 0 to 20° C. That is, the silica-based fine particle dispersion may be stirred, the cerium metal salt may be added continuously or intermittently while maintaining the temperature higher than 20° C. and not higher than 98° C., the pH may be 5.0 to 10.0, and the redox potential may be 50 to 500 mV, and then the cerium metal salt may be added continuously or intermittently while maintaining the temperature at 0 to 20° C., the pH may be 5.0 to 9.0, and the redox potential may be 50 to 500 mV, to obtain the precursor particle dispersion. This is because, even when step 1 is carried out in this manner, it is easier to obtain the dispersion of the present invention containing the composite fine particles of the present invention in which the coefficient of variation in the particle size distribution of the child particles is at a suitable value. When treating at a temperature higher than 20°C and not higher than 98°C, the preferred values and adjustment methods for pH and oxidation-reduction potential are the same as when treating at a temperature of 0 to 20°C. Even when the temperature is changed during blending in this way, as long as a blending step at a temperature of 0 to 20°C is included, the composite fine particles will be produced by the same mechanism as described above.
[0116] When the reaction temperature is between 0 and 20°C, the reactivity of cerium with silica is suppressed, resulting in the production of large-sized ultrafine CeO particles. However, if the compounding temperature is subsequently maintained above 20°C but below 98°C and a cerium metal salt is added, the reactivity of cerium with silica increases, promoting silica dissolution. This inhibits ceria crystal growth, resulting in the production of small-sized ultrafine CeO particles. Thus, while maintaining a reaction temperature between 0 and 20°C during the compounding process (Step 1), changing the reaction temperature to above 20°C but below 98°C and adding a cerium metal salt can broaden the particle size distribution of the CeO particles and ceria subparticles. Note that, as long as the compounding temperature is between 0 and 20°C and a step of adding a cerium metal salt is included, the reaction at a temperature above 20°C but below 98°C can be performed before or after the reaction at 0 to 20°C, and the temperature can be changed three or more times. Furthermore, when the reaction temperature is changed to two or more stages, the amount of cerium metal salt added in the reaction step at 0 to 20°C is preferably in the range of 10 to 90 mass% of the total amount of cerium metal salt added. If this range is exceeded, the proportion of large (or small) CeO2 ultrafine particles and ceria elementary particles decreases, and the particle size distribution does not become very wide.
[0117] The precursor particle dispersion obtained in step 1 may be further diluted or concentrated with pure water, ion-exchanged water, or the like before being subjected to step 2.
[0118] The solid content concentration in the precursor particle dispersion is preferably 1 to 27% by mass.
[0119] If desired, the precursor particle dispersion may be deionized using a cation exchange resin, an anion exchange resin, an ultrafiltration membrane, an ion exchange membrane, or by centrifugation.
[0120] <Process 2> In step 2, the precursor particle dispersion liquid is dried and then fired at 850 to 1100°C.
[0121] The drying method is not particularly limited. Drying can be carried out using a conventionally known dryer. Specifically, a box dryer, a band dryer, a spray dryer, or the like can be used. Preferably, the pH of the precursor particle dispersion before drying is set to 6.0 to 7.0, because the surface activity can be suppressed when the pH of the precursor particle dispersion before drying is set to 6.0 to 7.0.
[0122] After drying, the firing temperature is 850 to 1100°C, preferably 910 to 1100°C, more preferably 920 to 1090°C, and most preferably 930 to 970°C. Firing within this temperature range ensures sufficient ceria crystallization, and the cerium-containing silica layer in which the ceria subparticles are dispersed has an appropriate thickness. This allows the cerium-containing silica layer to be firmly bonded to the base particles, making it difficult for the subparticles dispersed in the cerium-containing silica layer to fall off. Furthermore, firing within this temperature range makes it difficult for cerium hydroxide and other substances to remain. If this temperature is too high, abnormal growth of ceria crystals may occur, the cerium-containing silica layer may become too thick, the amorphous silica constituting the base particles may crystallize, or the particles may fuse together.
[0123] Although alkali metals, alkaline earth metals, sulfates, and the like can be added as flux components during firing to promote ceria crystal growth, the flux components can cause metal contamination and corrosion of the polishing substrate. Therefore, the content of the flux components during firing is preferably 100 ppm or less, more preferably 50 ppm or less, and most preferably 40 ppm or less per precursor particle (dry). The flux component may utilize the carry-in from the colloidal silica of the raw material or be used as an alkali for neutralizing the cerium metal salt during formulation. However, when an alkali metal or alkaline earth metal coexists during formulation, the polymerization of silica fine particles is promoted and densified, resulting in a decrease in the reactivity between cerium hydroxide and silica fine particles. Furthermore, since the surface of the silica fine particles is protected by an alkali metal or alkaline earth metal, the reactivity with cerium hydroxide and the like is suppressed, and a cerium-containing silica layer tends not to be formed. Moreover, since the dissolution of silica is suppressed during formulation, it becomes difficult for silicon atoms to dissolve in solid solution in the ceria sub-particles.
[0124] Also, when firing in such a temperature range, silicon atoms dissolve in solid solution in the crystalline ceria, which is the main component of the sub-particles. Therefore, regarding the cerium atoms and silicon atoms contained in the sub-particles, when the cerium-silicon atomic distance is R1 and the cerium-cerium atomic distance is R2, a relationship of R1 < R2 can be satisfied.
[0125] In Step 2, a solvent is added to the fired body obtained by firing, and wet pulverization treatment is performed within a pH range of 8.6 to 10.8. Here, before subjecting the fired body to wet pulverization treatment, the fired body may be dry pulverized and then wet pulverization treatment may be performed.
[0126] As the dry pulverization device, conventionally known devices can be used. For example, an attritor, a ball mill, a vibration mill, a vibration ball mill, etc. can be mentioned.
[0127] Conventionally known wet crushing devices can be used, including, for example, batch bead mills such as basket mills, horizontal, vertical, and annular continuous bead mills, sand grinder mills, ball mills, rotor-stator homogenizers, ultrasonic dispersion homogenizers, and wet media agitation mills (wet crushers) such as impact crushers that collide fine particles in a dispersion liquid. Examples of beads used in wet media agitation mills include beads made from raw materials such as glass, alumina, zirconia, steel, flint, and organic resins. The solvent used when wet-disintegrating the fired body is water and / or an organic solvent. For example, it is preferable to use water such as pure water, ultrapure water, or ion-exchanged water. The solid content concentration here is not particularly limited, but is preferably in the range of 0.3 to 50 mass %.
[0128] When the fired body is subjected to wet-disintegration, it is preferable to carry out the wet-disintegration while maintaining the pH of the solvent at 8.6 to 10.8. Maintaining the pH within this range makes it easier to finally obtain a ceria-based composite microparticle dispersion that, when subjected to cationic colloid titration, gives a streaming potential curve, as expressed by the above formula (1), in which the ratio (ΔPCD / V) of the streaming potential change (ΔPCD) to the amount of cationic colloid titrant added at the titration point (V) is -110.0 to -15.0. That is, it is preferable to perform disintegration to the extent that the dispersion of the present invention corresponding to the above-mentioned preferred embodiment is obtained. As mentioned above, when the dispersion of the present invention corresponding to the preferred embodiment is used as an abrasive, the polishing rate is further improved. Regarding this, the present inventors speculate that the polishing rate is further improved and the shedding of ceria child particles can be controlled by appropriately thinning the cerium-containing silica layer on the surface of the composite fine particles of the present invention and / or by appropriately exposing child particles on a portion of the surface of the composite fine particles. Furthermore, they speculate that during disintegration, silica in the cerium-containing silica layer dissolves and re-deposits, forming a soft, easily soluble silica layer as the outermost layer. This easily soluble silica layer improves frictional force by adhering to the substrate, thereby improving the polishing rate. Furthermore, they speculate that the thin or peeled cerium-containing silica layer makes the child particles more likely to detach during polishing to some extent. The ΔPCD / V is more preferably -100.0 to -15.0, and even more preferably -100.0 to -20.0. If the calcined powder is merely loosened without going through a wet crushing step such as step 2, if only dry crushing and pulverization are performed, or if wet crushing is performed but the pH is outside the specified range, it is difficult for ΔPCD / V to fall within the range of -100.0 to -15, and furthermore it is difficult for a soft, easily soluble silica layer to be formed.
[0129] In step 2, it is preferable to add the solvent to the fired body, wet crush the mixture at a pH of 8.6 to 10.8, then centrifugal separate the mixture at a relative centrifugal acceleration of 300 G or more, and then remove the precipitated components to obtain a ceria-based composite microparticle dispersion. The classification by centrifugation is preferably carried out at a relative centrifugal acceleration of 300 G or more. After the centrifugation, the sedimentary components are preferably removed to obtain a ceria-based composite microparticle dispersion. There is no particular upper limit to the relative centrifugal acceleration, but in practice it is used at 10,000 G or less. Such a centrifugal acceleration makes it difficult for coarse particles to remain in the ceria-based composite microparticle dispersion, and as a result, when the ceria-based composite microparticle dispersion is used for polishing purposes such as an abrasive, scratches are unlikely to occur.
[0130] In the present invention, the ceria-based composite microparticle dispersion obtained by the above-mentioned production method can be further dried to obtain ceria-based composite microparticles. The drying method is not particularly limited, and for example, drying can be performed using a conventionally known dryer.
[0131] The dispersion of the present invention can be obtained by the production method of the present invention.
[0132] <Polishing abrasive dispersion> The liquid containing the dispersion of the present invention can be preferably used as a polishing abrasive dispersion (hereinafter also referred to as "polishing abrasive dispersion of the present invention"). In particular, it can be preferably used as a polishing abrasive dispersion for planarizing a semiconductor substrate on which an SiO2 insulating film is formed. In addition, it can be preferably used as a polishing slurry by adding a chemical component to control the polishing performance.
[0133] The abrasive dispersion for polishing of the present invention has excellent effects such as a high polishing rate when polishing semiconductor substrates and the like, less scratches on the polished surface during polishing, and less abrasive particles remaining on the substrate.
[0134] The polishing abrasive dispersion of the present invention contains water and / or an organic solvent as a dispersion solvent. It is preferable to use water, such as pure water, ultrapure water, or ion-exchanged water, as the dispersion solvent. Furthermore, the polishing abrasive dispersion of the present invention can be suitably used as a polishing slurry by adding at least one additive selected from the group consisting of a polishing accelerator, a surfactant, a heterocyclic compound, a pH adjuster, and a pH buffer to control the polishing performance.
[0135] <Polishing accelerator> The polishing abrasive dispersion of the present invention can be used as polishing slurry by adding conventionally known polishing accelerators as needed, depending on the type of polishing material.Such examples include hydrogen peroxide, peracetic acid, urea peroxide, etc. and their mixtures.When using the polishing compound containing such polishing accelerators as hydrogen peroxide, when the polishing material is metal, it can effectively improve the polishing speed.
[0136] Other examples of the polishing accelerator include inorganic acids such as sulfuric acid, nitric acid, phosphoric acid, oxalic acid, and hydrofluoric acid, organic acids such as acetic acid, and the sodium, potassium, ammonium, and amine salts of these acids, and mixtures thereof. In the case of a polishing composition containing such a polishing accelerator, when polishing a workpiece made of multiple components, the polishing rate of a specific component of the workpiece can be accelerated, thereby finally obtaining a flat polished surface.
[0137] When the abrasive grain dispersion for polishing of the present invention contains a polishing accelerator, the content thereof is preferably 0.1 to 10 mass %, more preferably 0.5 to 5 mass %.
[0138] <Surfactant and / or hydrophilic compound> To improve the dispersibility and stability of the polishing abrasive dispersion of the present invention, cationic, anionic, nonionic, or amphoteric surfactants or hydrophilic compounds can be added. Both surfactants and hydrophilic compounds have the effect of reducing the contact angle with the surface to be polished and promoting uniform polishing. Examples of surfactants and / or hydrophilic compounds that can be used include those selected from the following group:
[0139] Examples of anionic surfactants include carboxylates, sulfonates, sulfates, and phosphates. Examples of carboxylates include soaps, N-acylamino acid salts, polyoxyethylene or polyoxypropylene alkyl ether carboxylates, and acylated peptides. Examples of sulfonates include alkyl sulfonates, alkylbenzene and alkylnaphthalene sulfonates, naphthalene sulfonates, sulfosuccinates, α-olefin sulfonates, and N-acylsulfonates. Examples of sulfates include sulfated oils, alkyl sulfates, alkyl ether sulfates, polyoxyethylene or polyoxypropylene alkyl allyl ether sulfates, and alkylamide sulfates. Examples of phosphates include alkyl phosphates and polyoxyethylene or polyoxypropylene alkyl allyl ether phosphates.
[0140] Examples of cationic surfactants include aliphatic amine salts, aliphatic quaternary ammonium salts, benzalkonium chloride salts, benzethonium chloride, pyridinium salts, and imidazolinium salts; and examples of amphoteric surfactants include carboxybetaine type, sulfobetaine type, aminocarboxylate salts, imidazolinium betaine, lecithin, and alkylamine oxide.
[0141] Examples of nonionic surfactants include ether type, ether ester type, ester type, and nitrogen-containing type. Examples of ether type surfactants include polyoxyethylene alkyl and alkylphenyl ethers, alkylaryl formaldehyde condensed polyoxyethylene ethers, polyoxyethylene polyoxypropylene block polymers, and polyoxyethylene polyoxypropylene alkyl ethers. Examples of ether ester type surfactants include polyoxyethylene ethers of glycerin esters, polyoxyethylene ethers of sorbitan esters, and polyoxyethylene ethers of sorbitol esters. Examples of ester type surfactants include polyethylene glycol fatty acid esters, glycerin esters, polyglycerin esters, sorbitan esters, propylene glycol esters, and sucrose esters. Examples of nitrogen-containing surfactants include fatty acid alkanolamides, polyoxyethylene fatty acid amides, and polyoxyethylene alkylamides. Other examples include fluorine-based surfactants.
[0142] The surfactant is preferably an anionic surfactant or a nonionic surfactant, and the salt includes ammonium salt, potassium salt, sodium salt, etc., with ammonium salt and potassium salt being particularly preferred.
[0143] Further examples of other surfactants, hydrophilic compounds, etc. include esters such as glycerin esters, sorbitan esters, and alanine ethyl esters; ethers such as polyethylene glycol, polypropylene glycol, polytetramethylene glycol, polyethylene glycol alkyl ethers, polyethylene glycol alkenyl ethers, alkyl polyethylene glycols, alkyl polyethylene glycol alkyl ethers, alkyl polyethylene glycol alkenyl ethers, alkenyl polyethylene glycols, alkenyl polyethylene glycol alkyl ethers, alkenyl polyethylene glycol alkenyl ethers, polypropylene glycol alkyl ethers, polypropylene glycol alkenyl ethers, alkyl polypropylene glycols, alkyl polypropylene glycol alkyl ethers, alkyl polypropylene glycol alkenyl ethers, and alkenyl polypropylene glycols; polysaccharides such as alginic acid, pectinic acid, carboxymethylcellulose, curdlan, and pullulan; glycine ammonium salts and glycine sodium salts; amino acid salts such as ammonium salts; polycarboxylic acids and their salts such as polyaspartic acid, polyglutamic acid, polylysine, polymalic acid, polymethacrylic acid, ammonium salts of polymethacrylic acid, sodium salts of polymethacrylic acid, polyamic acid, polymaleic acid, polyitaconic acid, polyfumaric acid, poly(p-styrenecarboxylic acid), polyacrylic acid, polyacrylamide, aminopolyacrylamide, ammonium salts of polyacrylic acid, sodium salts of polyacrylic acid, polyamic acid, ammonium salts of polyamic acid, sodium salts of polyamic acid, and polyglyoxylic acid; vinyl polymers such as polyvinyl alcohol, polyvinylpyrrolidone, and polyacrolein; sulfonic acids and their salts such as ammonium salts of methyl taurate, sodium salts of methyl taurate, sodium salts of methyl sulfate, ethylammonium sulfate, butylammonium sulfate, sodium salts of vinyl sulfonate, sodium salts of 1-allylsulfonate, sodium salts of 2-allylsulfonate, sodium salts of methoxymethylsulfonate, ammonium salts of ethoxymethylsulfonate, and sodium salts of 3-ethoxypropylsulfonate;Examples include amides such as propionamide, acrylamide, methylurea, nicotinamide, succinamide, and sulfanilamide;
[0144] When the substrate to be polished is a glass substrate or the like, any surfactant can be suitably used. However, when the substrate is a silicon substrate for a semiconductor integrated circuit or the like, and the influence of contamination by alkali metals, alkaline earth metals, halides, or the like must be avoided, it is desirable to use an acid or its ammonium salt surfactant.
[0145] When the polishing abrasive dispersion of the present invention contains a surfactant and / or a hydrophilic compound, the total content thereof is preferably 0.001 to 10 g, more preferably 0.01 to 5 g, and particularly preferably 0.1 to 3 g, per liter of the polishing abrasive dispersion.
[0146] The content of the surfactant and / or hydrophilic compound is preferably 0.001 g or more per liter of the polishing abrasive dispersion in order to obtain a sufficient effect, and is preferably 10 g or less in order to prevent a decrease in the polishing rate.
[0147] The surfactant or hydrophilic compound may be used alone or in combination with two or more kinds.
[0148] <Heterocyclic compounds> Regarding the abrasive grain dispersion liquid of the present invention, when the substrate to be polished contains metal, in order to form a passive layer or a dissolution inhibition layer on the metal and suppress the erosion of the substrate to be polished, a heterocyclic compound may be contained. Here, the "heterocyclic compound" is a compound having a heterocyclic ring containing one or more heteroatoms. The heteroatom means an atom other than a carbon atom or a hydrogen atom. The heterocyclic ring means a cyclic compound having at least one heteroatom. The heteroatom means only an atom that forms a constituent part of the ring system of the heterocyclic ring, and does not mean an atom that is located outside the ring system, separated from the ring system by at least one non-conjugated single bond, or is a part of a further substituent of the ring system. Preferred heteroatoms include, but are not limited to, a nitrogen atom, a sulfur atom, an oxygen atom, a selenium atom, a tellurium atom, a phosphorus atom, a silicon atom, and a boron atom. As examples of the heterocyclic compound, imidazole, benzotriazole, benzothiazole, tetrazole, etc. can be used. More specifically, 1,2,3,4-tetrazole, 5-amino-1,2,3,4-tetrazole, 5-methyl-1,2,3,4-tetrazole, 1,2,3-triazole, 4-amino-1,2,3-triazole, 4,5-diamino-1,2,3-triazole, 1,2,4-triazole, 3-amino 1,2,4-triazole, 3,5-diamino-1,2,4-triazole, etc. can be mentioned, but are not limited thereto.
[0149] Regarding the content when a heterocyclic compound is blended in the abrasive grain dispersion liquid of the present invention, it is preferably 0.001 to 1.0% by mass, more preferably 0.001 to 0.7% by mass, and even more preferably 0.002 to 0.4% by mass.
[0150] <pH adjuster> In order to enhance the effects of the above additives, etc., an acid or a base and their salt compounds can be added as necessary to adjust the pH of the polishing composition.
[0151] When adjusting the pH of the abrasive grain dispersion liquid of the present invention to pH 7 or higher, an alkaline substance is used as the pH adjuster. Desirably, amines such as sodium hydroxide, aqueous ammonia, ammonium carbonate, ethylamine, methylamine, triethylamine, and tetramethylamine are used.
[0152] When adjusting the pH of the abrasive grain dispersion liquid of the present invention to less than pH 7, an acidic substance is used as the pH adjuster. For example, mineral acids such as hydrochloric acid and nitric acid, and hydroxy acids such as acetic acid, lactic acid, citric acid, malic acid, tartaric acid, and glyceric acid are used.
[0153] <pH buffer> In order to keep the pH value of the abrasive grain dispersion liquid of the present invention constant, a pH buffer may be used. As the pH buffer, for example, phosphates and borates or organic acid salts such as ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ammonium tetraborate tetrahydrate can be used.
[0154] Examples of the dispersion solvent for the abrasive grain dispersion of the present invention include alcohols such as methanol, ethanol, isopropanol, n-butanol, and methyl isocarbinol; ketones such as acetone, 2-butanone, ethyl amyl ketone, diacetone alcohol, isophorone, and cyclohexanone; amides such as N,N-dimethylformamide and N,N-dimethylacetamide; ethers such as diethyl ether, isopropyl ether, tetrahydrofuran, 1,4-dioxane, and 3,4-dihydro-2H-pyran; glycol ethers such as 2-methoxyethanol, 2-ethoxyethanol, 2-butoxyethanol, and ethylene glycol dimethyl ether; Examples of organic solvents that can be used include glycol ether acetates such as 2-methoxyethyl acetate, 2-ethoxyethyl acetate, and 2-butoxyethyl acetate; esters such as methyl acetate, ethyl acetate, isobutyl acetate, amyl acetate, ethyl lactate, and ethylene carbonate; aromatic hydrocarbons such as benzene, toluene, and xylene; aliphatic hydrocarbons such as hexane, heptane, isooctane, and cyclohexane; halogenated hydrocarbons such as methylene chloride, 1,2-dichloroethane, dichloropropane, and chlorobenzene; sulfoxides such as dimethyl sulfoxide; and pyrrolidones such as N-methyl-2-pyrrolidone and N-octyl-2-pyrrolidone. These may also be mixed with water.
[0155] The solids concentration in the polishing abrasive dispersion of the present invention is preferably in the range of 0.3 to 50 mass %. If this solids concentration is too low, the required polishing rate may not be achieved. Conversely, if the solids concentration is too high, the polishing rate is rarely improved any more. [Example]
[0156] The present invention will be described below based on examples, but the present invention is not limited to these examples.
[0157] <Experiment 1> First, the details of the measurement and test methods used in the Examples and Comparative Examples will be described. The following measurement and test results for each Example and Comparative Example are shown in Table 1.
[0158] [Area of the arched shape X of the ceria composite particle (S x ), area (S0), chord length, arrow height and total arc length (w), and chord length, arrow height and total arc length (w) of the arcuate shape Y of the silica microparticles. For the ceria-based composite particles obtained in the examples and comparative examples, the area (S x ) and the area of the pseudo-spherical Celica composite particles (S0), and the area ratio (S x The length of the chord, the height of the arrow, and the total length of the arc (w) of the arched figure X were also calculated. Furthermore, the length of the chord, the height of the arrow, and the total length of the arc (w) of the arched figure Y were calculated in the same way for the silica microparticles.
[0159] [Component analysis] [Measurement of SiO2 and CeO2 contents] The SiO2 content in the ceria-based composite microparticles was determined by subjecting the ceria-based composite microparticle dispersion to ignition loss at 1000°C, determining the mass of the solids, and then measuring the Ce content by the standard addition method using an ICP plasma emission spectrometer (e.g., SII, SPS5520) described below to calculate the CeO2 mass%. The SiO2 content was determined by assuming that the solid components other than CeO2 were SiO2. The SiO2 content, CeO2 content, and parts by mass of ceria per 100 parts by mass of silica in the ceria-based composite microparticles were calculated based on the CeO2 content and SiO2 content determined here. The solids concentration of the ceria-based composite microparticle dispersion can also be determined here.
[0160] A method for measuring the Ce content by the standard addition method using an ICP plasma emission spectrometer (for example, SPS5520 manufactured by SII) will be described. First, approximately 1 g of a sample (adjusted to 20% solids by mass) consisting of ceria-based composite microparticles or a ceria-based composite microparticle dispersion is placed on a platinum dish. 3 ml of phosphoric acid, 5 ml of nitric acid, and 10 ml of hydrofluoric acid are added, and the mixture is heated on a sand bath. After drying, a small amount of water and 50 ml of nitric acid are added to dissolve the mixture, and the resulting solution is placed in a 100 ml measuring flask. Water is then added to the flask to make a final volume of 100 ml. Next, 10 ml of the resulting solution is aliquoted into a 20 ml measuring flask five times, yielding five 10 ml aliquots. Ce is then measured using an ICP plasma optical emission spectrometer (e.g., SII, SPS5520) using the standard addition method. A blank is also measured in the same manner, and the measured Ce value is calculated by subtracting the blank.
[0161] [X-ray diffraction method, measurement of average crystallite size] The ceria-based composite microparticle dispersion or silica microparticles obtained in the examples and comparative examples were dried using a conventionally known dryer, and the obtained powder was pulverized in a mortar for 10 minutes. The X-ray diffraction pattern was obtained using an X-ray diffractometer (RINT1400, manufactured by Rigaku Corporation) to identify the crystal type. In addition, the full width at half maximum of the peak of the (111) plane (near 2θ=28 degrees) in the obtained X-ray diffraction pattern was measured by the above-mentioned method, and the average crystallite diameter was calculated by the Scherrer formula.
[0162] <Average particle size> (1) The average particle diameter of the ceria-based composite microparticles contained in the ceria-based composite microparticle dispersions obtained in the Examples and Comparative Examples was measured by the above-mentioned image analysis method based on a photographic projection obtained by photographing the ceria-based composite microparticles using a transmission electron microscope. An electron microscope photograph (transmission electron microscope photograph) of the composite microparticles of the present invention magnified 100,000 times is prepared, and for 50 random particles on the image, the maximum diameter of the particle is taken as the major axis, and the length of that particle is measured and defined as the major axis (DL). A point is determined on the major axis that divides the major axis in half, and two points where a line perpendicular to that intersection with the outer edge of the particle are found. The distance between these two points is measured and defined as the minor axis (DS). The geometric mean value of the major axis (DL) and the minor axis (DS) is then calculated and defined as the particle diameter of the particle. The particle diameters of 50 particles are measured in this manner, and the value obtained by simply averaging these values is defined as the average particle diameter. (2) The average particle diameter of the pseudo-spherical ceria-based composite microparticles contained in the ceria-based composite microparticle dispersions obtained in the Examples and Comparative Examples was also measured by the image analysis method described above based on a photographic projection obtained by photographing using a transmission electron microscope. However, in measuring the average particle diameter of the pseudo-spherical ceria-based composite microparticles, 50 pseudo-spherical ceria-based composite microparticles were selected from the ceria-based composite microparticles shown in the photographic projection obtained by photographing using a transmission electron microscope, and measurement and calculation were carried out in the same manner as described above. (3) Regarding the average particle size of the base particles of the ceria-based composite microparticles in the ceria-based composite microparticle dispersions obtained in the Examples and Comparative Examples and the average particle size of the base particles of the pseudo-spherical ceria-based composite microparticles contained in the ceria-based composite microparticle dispersions obtained in the Examples and Comparative Examples, the average particle size of the silica sol (silica microparticle dispersion) used as a raw material for producing the ceria-based composite microparticle dispersion was measured and calculated by the methods (1) and (2) above.
[0163] <Coefficient of variation> The coefficient of variation was determined by the method described above.
[0164] <Specific surface area> The specific surface area of the ceria-based composite particles obtained in the examples and comparative examples was measured by the above-mentioned method, using a surface area measuring device (manufactured by Mountech Co., Ltd., product number: Mascsorb HM-1220). In the present invention, the specific surface area means a value obtained by measurement using such a method, unless otherwise specified.
[0165] [Number ratio of pseudo-spherical defective particles] Prepare an electron micrograph of the composite microparticle dispersion of the present invention magnified 100,000 times, and for 50 particles on the image, determine whether they correspond to pseudo-spherical defective particles. Then, obtain the number ratio of pseudo-spherical defective particles. That is, the ratio of pseudo-spherical defective particles in 50 particles was calculated.
[0166] [Polishing test method] <Polishing of SiO2 film> A polishing abrasive dispersion containing the ceria-based composite microparticle dispersion obtained in each of the examples and comparative examples was prepared. Here, the solid content concentration was 0.6% by mass, and nitric acid was added to adjust the pH to 5.0. Next, as the polished substrate, a substrate having a SiO2 insulating film (thickness: 1 μm) formed by a thermal oxidation method was prepared. Next, this polished substrate was set in a polishing apparatus (manufactured by Nanofactor Co., Ltd., NF300), and using a polishing pad (manufactured by Nitta Haas Co., Ltd., "IC-1000 / SUBA400 concentric circle type"), polishing was performed by supplying the polishing abrasive dispersion at a rate of 50 ml / min for 1 minute at a substrate load of 0.5 MPa and a table rotation speed of 90 rpm. Then, the weight change of the polished substrate before and after polishing was obtained, and the polishing rate was calculated.
[0167] [Polished substrate surface roughness] The smoothness (surface roughness Ra) of the surface of the polished substrate obtained by performing the SiO2 film polishing test as described above was measured using an atomic force microscope (AFM, manufactured by Hitachi High-Technologies Corporation). Since the smoothness and the surface roughness are generally in a proportional relationship, the surface roughness is described in Table 1.
[0168] Examples are described below.
[0169] <Example 1> [Preparation of silica-based microparticle dispersion containing pseudo-spherical defective silica microparticles] 451 g of ion-exchanged water was added to 500 g of silica sol (manufactured by JGC Catalysts and Chemicals Co., Ltd.: Spherica Slurry SS-300, average particle size 341 nm) to obtain a diluted slurry. Next, an aqueous sodium hydroxide solution was added to this diluted slurry to adjust the pH to 9.6, and then wet-grinding was carried out for 900 minutes in a wet-grinding machine (a batch-type benchtop sand mill manufactured by Kanpe Co., Ltd.) using zirconia beads of φ0.05 mm (manufactured by Nikkato Corporation). During the wet-grinding, an aqueous sodium hydroxide solution was added to maintain the pH at 9.5 to 10.5.
[0170] After crushing, the beads were separated by passing them through a 44-mesh wire net. Figure 3(a) shows an SEM image (100,000 magnification) of the silica particles dispersed in the resulting silica-based particle dispersion, and Figure 3(b) shows a TEM image (100,000 magnification). As shown in Figure 3, the silica microparticles were pseudo-spherical. That is, when the silica microparticles were inscribed, an area ratio of 1.0 to 1.5 times was observed, and an arch-shaped figure Y with an arrow height of 174 nm and a chord length of 285 nm was observed. The average particle size of the silica particles was 232 nm, and the average particle size of the pseudo-spherical particles was 207 nm. 3, it can be seen that the silica microparticles used in Example 1 are at least partially inscribed in the chord of the arched figure Y. It can also be seen that the silica microparticles are inscribed in a point D on the arc that bisects the entire length of the arc of the arched figure Y, and are at least partially inscribed in both the arc curves on one side and the arc curves on the other side of the arc with the point D as the center. Furthermore, it can be seen from FIG. 3 that the silica fine particles used in Example 1 are inscribed in at least 20% of the chord of the arcuate figure Y. Furthermore, the solid content was 4.6 mass % and the weight was 1375 g.
[0171] Next, 41 g of a cation exchange resin (manufactured by Mitsubishi Chemical Corporation) was added to 1286 g of the resulting dispersion of pseudo-spherical silica particles, and the mixture was stirred for 60 minutes. After ion exchange, the resin was separated by passing it through a 44-mesh wire screen to obtain a cation-exchanged liquid having a solids concentration of 4.0% by mass, a pH of 3.1, and a weight of 1,440 g. Next, 50 g of anion exchange resin (manufactured by Mitsubishi Chemical Corporation) was added to 1440 g of the obtained cation exchange liquid, and the mixture was stirred for 60 minutes. After ion exchange, the resin was separated by passing it through a 44-mesh wire screen to obtain an anion-exchanged liquid, which had a solids concentration of 3.0% by mass, a pH of 4.5, and a weight of 1891 g. Next, an aqueous ammonia solution was added to the resulting anion-exchanged liquid to adjust the pH to 9.1. The liquid obtained here will hereinafter also be referred to as Liquid A-1.
[0172] Next, ion-exchanged water was added to cerium (III) nitrate hexahydrate (Kanto Chemical Co., Ltd., 4N high-purity reagent) to obtain an aqueous solution of cerium nitrate with a CeO2 content of 3.0% by mass (hereinafter also referred to as Solution B-1). Next, Solution B-1 (2293 g, 70 g of dry CeO2) was added to Solution A-1 (1894 g) over 27 hours while stirring and maintaining the temperature at 15.5°C. During this time, the solution temperature was maintained at 15.5°C, and 3% aqueous ammonia was added as needed to maintain the pH between 5.0 and 9.0. After the addition was complete, the solution was aged for 4 hours at a temperature of 15.5°C. During the addition of Solution B-1 and aging, air was blown into the prepared solution to maintain the redox potential between 50 and 400 mV. After that, washing was performed by using an ultrafiltration membrane while replenishing ion-exchanged water. The precursor particle dispersion obtained after washing had a solid content of 5.0% by mass, a pH of 7.5 (at 25°C), and an electrical conductivity of 20 μs / cm (at 25°C).
[0173] Next, the obtained precursor particle dispersion was adjusted to pH 6.5 using an aqueous acetic acid solution, dried in a dryer at 120°C for 15 hours, and then calcined in a muffle furnace at 950°C for 2 hours to obtain a powder (calcined body).
[0174] Next, 300 g of ion-exchanged water was added to 88 g of the powder (calcined body) obtained after calcination, and the pH was adjusted to 9.2 using a 3% aqueous ammonia solution. After that, wet-crushing was carried out for 180 minutes using φ0.25 mm quartz beads (manufactured by Daiken Chemical Industry Co., Ltd.) in a wet-crushing machine (a batch-type benchtop sand mill manufactured by Kanpe Co., Ltd.). After crushing, the beads were separated by passing the mixture through a 44-mesh wire net. The solid content of the resulting crushed sintered body dispersion was 7.1% by mass and the weight was 1,090 g. During crushing, an aqueous ammonia solution was added to maintain the pH at 9.2.
[0175] Furthermore, the crushed sintered body dispersion was centrifuged at 1700 G for 102 seconds in a centrifuge (manufactured by Hitachi Koki Co., Ltd., model number "CR21G"), the light liquid was recovered, and the mixture was diluted to 200 g with ion-exchanged water. After that, the mixture was dispersed by ultrasonic irradiation for 3 hours to obtain a ceria-based composite microparticle dispersion. The average particle size of the ceria-based composite fine particles contained in the obtained ceria-based composite fine particle dispersion was 236 nm, and the average particle size of the pseudo-spherical particles among them was 209 nm. FIG. 4 shows an SEM image (100,000 times magnification) of the obtained ceria-based composite microparticles. As shown in FIG. 4, the ceria-based composite microparticles had a pseudo-spherical shape. That is, when the ceria-based composite microparticles were inscribed, the area ratio was 1.1 times, and an arched figure X was present, with an arrow height of 156 nm and a chord length of 275 nm. From FIG. 4, it can be seen that the ceria-based composite microparticles obtained in Example 1 were at least partially inscribed in the chord of arched figure X. It can also be seen that the ceria-based composite microparticles were inscribed in a point D on an arc that bisects the entire length of the arc of arched figure X, and at least partially inscribed in both the arc curves on one side and the opposite side of the arc centered on point D. Furthermore, it can be seen from FIG. 4 that the ceria-based composite fine particles obtained in Example 1 are inscribed in at least 20% of the chord of the arcuate figure X.
[0176] The ceria-based composite fine particle dispersion thus obtained was subjected to a polishing test, and the results are shown in Table 1.
[0177] Furthermore, the ceria-based composite microparticles contained in the ceria-based composite microparticle dispersion obtained in Example 1 were measured by X-ray diffraction. The obtained X-ray diffraction pattern is shown in Figure 5. As shown in Figure 5, a fairly sharp cerianite crystal pattern was observed in the X-ray diffraction pattern.
[0178] Furthermore, the ceria-based composite microparticles contained in the ceria-based composite microparticle dispersion obtained in Example 1 were subjected to STEM-EDS analysis, and it was confirmed that the ceria-based composite microparticles comprise mother particles, a cerium-containing silica layer on the surface of the mother particles, and child particles dispersed within the cerium-containing silica layer.
[0179] <Example 2> The same operation as in Example 1 was carried out, and the obtained sintered crushed dispersion was processed in a centrifuge (manufactured by Hitachi Koki Co., Ltd., model number "CR21G") at 1700 G for 102 seconds, and the heavy liquid was recovered and diluted to 59 g with ion-exchanged water, and then dispersed by ultrasonic irradiation to obtain a ceria-based composite microparticle dispersion.
[0180] The average particle size of the ceria-based composite fine particles contained in the obtained ceria-based composite fine particle dispersion was 236 nm, and the average particle size of the pseudo-spherical particles among them was 209 nm. Furthermore, SEM images of the resulting ceria-based composite particles were obtained, and it was confirmed that the ceria-based composite particles had a pseudo-spherical shape. That is, an arched figure X was present in which the area ratio when the ceria-based composite microparticles were inscribed was 1.1 times, the arrow height was 156 nm, and the chord length was 275 nm. Furthermore, from an SEM image of the obtained ceria-based composite microparticles, it was confirmed that the ceria-based composite microparticles obtained in Example 2 were at least partially inscribed in the chord of the arched figure X. Furthermore, it was confirmed that the ceria-based composite microparticles were inscribed in a point D on an arc that bisects the entire length of the arc of the arched figure X, and that they were at least partially inscribed in both the arc curves on one side and the opposite side of the arc with the point D as the center. Furthermore, from the SEM image of the obtained ceria-based composite particles, it was confirmed that the ceria-based composite particles obtained in Example 2 were inscribed in at least 20% of the chord of the arcuate figure X.
[0181] The ceria-based composite fine particle dispersion thus obtained was subjected to a polishing test, and the results are shown in Table 1.
[0182] Furthermore, the ceria-based composite microparticles contained in the ceria-based composite microparticle dispersion obtained in Example 2 were measured by X-ray diffraction, and the crystal pattern of cerianite could be observed.
[0183] <Comparative Example 1> Preparation of Silica Sol (60 nm) 12,090 g of ethanol and 6,363.9 g of ethyl orthosilicate were mixed to prepare a mixed solution a1. Next, 6,120 g of ultrapure water and 444.9 g of 29% ammonia water were mixed to obtain a mixed liquid b1. Next, 192.9 g of ultrapure water and 444.9 g of ethanol were mixed to prepare a bed water. The water bed was then adjusted to 75°C while being stirred, and mixed liquids a1 and b1 were added simultaneously so that the addition would be completed within 10 hours for each. After the addition was completed, the liquid temperature was maintained at 75°C for 3 hours for aging, and the solid content was then adjusted to obtain 9,646.3 g of silica sol with an SiO2 solid content of 19% by mass and an average particle size of 60 nm as measured by laser diffraction / scattering.
[0184] Preparation of silica microparticle dispersion (average particle diameter of silica microparticles: 108 nm) 2,733.3 g of methanol and 1,822.2 g of ethyl orthosilicate were mixed to prepare a mixed solution a2. Next, 1,860.7 g of ultrapure water and 40.6 g of 29% ammonia water were mixed to prepare a mixed liquid b2. Next, 59 g of ultrapure water and 1,208.9 g of methanol were mixed to prepare a bed of water, and 922.1 g of a silica fine particle dispersion liquid obtained in the previous step by dispersing silica fine particles having an average particle size of 60 nm in a solvent was added. The bed water containing the silica microparticle dispersion was then adjusted to 65°C while being stirred, and mixed liquid a2 and mixed liquid b2 were simultaneously added thereto so that the addition would be completed within 18 hours for each. After the addition was completed, the liquid temperature was maintained at 65°C for 3 hours for aging, and then the solid concentration (SiO2 solid concentration) was adjusted to 19 mass% to obtain 3,600 g of a high-purity silica microparticle dispersion. The silica microparticles contained in this high-purity silica microparticle dispersion had an average particle diameter of 108 nm as measured by dynamic light scattering (PAR-III manufactured by Otsuka Electronics Co., Ltd.) The minor axis / major axis ratio of the silica microparticles was also measured based on a transmission electron microscope photograph, and was found to be 1.0. In addition, the contents of Na, Ag, Al, Ca, Cr, Cu, Fe, K, Mg, Ni, Ti, Zn, Zr, U, Th, Cl, NO3, SO4 and F were measured using atomic absorption spectrometry, ICP (inductively coupled plasma atomic emission spectrometry), potentiometric titration or ion chromatography, and all were found to be below 1 ppm.
[0185] Next, 114 g of cation exchange resin (SK-1BH manufactured by Mitsubishi Chemical Corporation) was gradually added to 1,053 g of this high-purity silica particle dispersion (average particle diameter of silica particles: 108 nm), and the mixture was stirred for 30 minutes to separate the resin. The pH at this time was 5.1. Ultrapure water was added to the obtained silica fine particle dispersion to obtain 6,000 g of A-2 liquid having an SiO2 solid content concentration of 3 mass %.
[0186] Next, ion-exchanged water was added to cerium (III) nitrate hexahydrate (Kanto Chemical Co., Ltd., 4N high-purity reagent) to obtain a B-2 solution with a CeO2 content of 2.5% by mass.
[0187] Next, liquid A-2 (6,000 g) was heated to 50°C, and liquid B-2 (8,453 g, equivalent to 117.4 parts by mass of CeO2 per 100 parts by mass of SiO2) was added thereto over 18 hours while stirring. During this time, the liquid temperature was maintained at 50°C, and 3% aqueous ammonia was added as necessary to maintain the pH at 7.85. During the addition of liquid B-2 and during aging, air was blown into the prepared liquid to maintain a positive oxidation-reduction potential. After the addition of B-2 liquid was completed, the liquid temperature was raised to 93°C and aged for 4 hours. After aging, the mixture was left to cool indoors and then cooled to room temperature. After that, the mixture was washed using an ultrafiltration membrane while replenishing with ion-exchanged water. The precursor particle dispersion obtained after washing had a solids concentration of 7% by mass, a pH of 9.1 (at 25°C), and an electrical conductivity of 67 μs / cm (at 25°C).
[0188] Next, a 5% by mass aqueous solution of acetic acid was added to the obtained precursor particle dispersion to adjust the pH to 6.5, and the mixture was dried in a dryer at 100°C for 16 hours, and then calcined in a muffle furnace at 1090°C for 2 hours to obtain a powder.
[0189] 310 g of the powder obtained after firing and 430 g of ion-exchanged water were placed in a 1 L beaker with a handle, to which a 3% aqueous ammonia solution was added, and the mixture was irradiated with ultrasound for 10 minutes in an ultrasonic bath while stirring to obtain a suspension with a pH of 10 (temperature: 25°C).
[0190] Next, 595 g of 0.25 mm quartz beads were placed in a mill (LMZ06, manufactured by Ashizawa Finetech Co., Ltd.), which had been previously cleaned and operated with water. The suspension was then loaded into the mill's charge tank (filling rate: 85%). Considering the ion-exchanged water remaining in the mill's milling chamber and piping, the concentration at the time of milling was 25% by mass. Wet crushing and grinding were performed under the following conditions: a disk peripheral speed of 12 m / sec, 25 passes, and a residence time of 0.43 minutes per pass. A 3% aqueous ammonia solution was added after each pass to maintain the pH of the suspension at 10 during crushing and grinding. In this way, a Celica-based composite microparticle dispersion with a solids concentration of 22% by mass was obtained. The resulting microparticle dispersion was then centrifuged for 1 minute at a relative centrifugal acceleration of 675 G in a centrifugal separator (manufactured by Hitachi Koki Co., Ltd., model number "CR21G") to remove sedimentary components and obtain a Celica-based composite microparticle dispersion.
[0191] FIG. 6(a) shows an SEM image (100,000 magnification) of the ceria-based composite fine particles obtained in Comparative Example 1, and FIG. 6(b) shows a TEM image (100,000 magnification).
[0192] [Table 1] [Industrial Applicability]
[0193] The ceria-based composite fine particles contained in the dispersion of the present invention do not contain coarse particles, and therefore have low scratching and a high polishing rate. Therefore, the polishing abrasive dispersion containing the dispersion of the present invention can be preferably used for polishing the surfaces of semiconductor devices such as semiconductor substrates and wiring substrates. Specifically, it can be preferably used for planarizing semiconductor substrates on which a silica film is formed.
Claims
1. A ceria-based composite microparticle dispersion comprising ceria-based composite microparticles having the following characteristics [1] to [3], wherein the proportion of the ceria-based composite microparticles in all particles in an electron microscope photograph is 5 to 20%: [1] The ceria-based composite microparticles have a mother particle, a cerium-containing silica layer on the surface of the mother particle, and child particles dispersed inside the cerium-containing silica layer, the mother particle being mainly composed of amorphous silica, and the child particles being mainly composed of crystalline ceria. [2] The ceria-based composite fine particles satisfy the following requirements: 1) On the electron microscope photograph, there is a circle inscribed with the image of the ceria-based composite fine particle, and further, the image of the ceria-based composite fine particle has the following relationship with respect to an arch-shaped figure X consisting of an arc on the circumference of the circle and a chord: (I) At least partially inscribed in the chord of the arcuate figure X. (II) It is inscribed in a point D on the arc that bisects the entire length of the arc of the arch-shaped figure X, and is at least partially inscribed in a circular curve on one side of the arc and a circular curve on the opposite side of the arc with the point D as the center. 2) The area of the arch shape X is 1.0 to 1.5 times the area of the image of the ceria-based composite fine particle, the length of the chord is 80 nm or more, and the height of the arrow is 40 nm or more. [3] The ceria-based composite fine particles have an average particle size of 50 to 350 nm as determined by an image analysis method.
2. 2. The ceria-based composite microparticle dispersion according to claim 1, wherein the ceria-based composite microparticles are inscribed in at least 20% of the chord of the arcuate figure X in an electron micrograph.
3. 3. The ceria-based composite microparticle dispersion according to claim 1 or 2, further comprising: an electron microscope photograph in which the ceria-based composite microparticles are at least partially inscribed in an arcuate curve extending along the arc for a length of w / 6 (w: total length of the arc) on both sides of a point D on the arc that bisects the total length of the arc; and the ceria-based composite microparticles are also at least partially inscribed in two arcuate curves connected to both ends of the arcuate curve.
4. The ceria-based composite microparticle dispersion according to any one of claims 1 to 3, further comprising ceria-based composite microparticles having the following characteristic [4]: [4] The ceria-based composite fine particles have a coefficient of variation of particle size distribution of child particles in the range of 15 to 50%.
5. 3. A polishing abrasive dispersion comprising the ceria-based composite fine particle dispersion according to claim 1.
6. 6. The polishing abrasive dispersion according to claim 5, which is used for planarizing a semiconductor substrate on which a silica film is formed.
7. A method for producing a ceria-based composite microparticle dispersion, comprising the steps of: Step 1: A step of stirring a silica-based fine particle dispersion liquid in which silica fine particles satisfying the following conditions 1), 2) and 3) are dispersed in a solvent, and continuously or intermittently adding a metal salt of cerium thereto while maintaining the temperature at 0 to 20°C, the pH at 5.0 to 9.0, and the oxidation-reduction potential at 50 to 500 mV, to obtain a precursor particle dispersion liquid containing precursor particles. 1) On the electron microscope photograph, there is a circle inscribed with the image of the silica fine particles, and further, the image of the silica fine particles has the following relationship with respect to an arch-shaped figure Y consisting of an arc on the circumference of the circle and a chord: (I) At least partially inscribed in the chord of the arcuate shape Y. (II) It is inscribed in a point D on the arc that bisects the entire length of the arc of the arch-shaped figure Y, and is at least partially inscribed in a circular curve on one side of the arc and a circular curve on the opposite side of the arc with the point D as the center. 2) The area of the arch shape Y is 1.0 to 1.5 times the area of the image of the silica fine particles, the length of the chord is 80 nm or more, and the height of the arrow is 40 nm or more. 3) The silica fine particles have an average particle size of 50 to 350 nm as determined by image analysis. Step 2: drying the precursor particle dispersion, calcining the precursor particle dispersion at 850 to 1,100° C., adding a solvent to the calcined product, and subjecting the resulting product to a wet-type disintegration treatment at a pH range of 8.6 to 10.8 to obtain the ceria-based composite microparticle dispersion.
8. 8. The method for producing a ceria-based composite microparticle dispersion according to claim 7, wherein the step 2 is a step of adding the solvent to the sintered body, performing a wet crushing treatment at a pH range of 8.6 to 10.8, performing a centrifugation treatment at a relative centrifugal acceleration of 300 G or more, and then removing sedimentation components to obtain the ceria-based composite microparticle dispersion.
9. 9. The method for producing a ceria-based composite microparticle dispersion according to claim 7 or 8, wherein the step 1 comprises adjusting a pH of a dispersion containing spherical silica particles to a range of 9.5 to 10.5, and wet-disintegrating the dispersion to obtain the silica microparticles.
Citation Information
Patent Citations
Silica-based composite particle and production method thereof
JP2013119131A
Ceria-based composite fine particle dispersion, production method thereof, and polishing abrasive grain dispersion comprising ceria-based composite fine particle dispersion
JP2019089670A
Method for producing cerium oxide ultrafine particles
JP2746861B2
Silica-based composite fine-particle dispersion, method for producing same, and polishing slurry including silica-based composite fine-particle dispersion
WO2016159167A1
Ceria-based composite fine particle dispersion, production method therefor, and polishing abrasive grain dispersion including ceria-based composite fine particle dispersion
WO2018221357A1